Artificial leather and its manufacturing method
By applying water-dispersed PU resin dispersion with specific structures on the fiber sheet and controlling the distribution of fibers and PU resins using water flow dispersion technology, the problem that artificial leather is difficult to meet the texture, density and moisture at the same time is solved, and multiple results are achieved Applicability of application scenarios.
Patent Information
- Application Number
- CN202080075011.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-30
- Filing Date
- 2020-10-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-10-27
AI Technical Summary
The prior art is difficult to satisfy the texture, density and moistness of artificial leather at the same time, making it difficult to achieve ideal standards while taking into account these characteristics.
The distribution of fibers and PU resins is controlled by applying a water-dispersed PU resin dispersion having a specific structure on the fiber sheet, including the use of nozzle hole spacing and turbulence of water flow in the water flow dispersion process, thereby forming appropriate PU resin blocks and fibers bundle structure.
It achieves excellent performance of artificial leather texture, denseness and moistness, and is suitable for a variety of application scenarios, such as interior decoration, automotive interior decoration, etc.
Smart Images

Figure CN114630935B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to artificial leather having good texture (softness and hardness value), dense feeling (dispersion of fiber bundles) and moist feeling (resin blocks of appropriate size) and a method for producing the same. Background Art
[0002] Artificial leather, which is mainly composed of fiber sheets (fibrous base materials) such as non-woven fabrics and polyurethane (hereinafter also referred to as PU) resin, has excellent characteristics that are difficult to achieve with natural leather, such as wrinkle-free, functionality, and homogeneity. It can be used in clothing, shoes, bags, and surface materials and interior materials of sheets for interior decoration, automobiles, airplanes, trains, etc., ribbons, badge base materials and other clothing materials.
[0003] As a method for manufacturing such artificial leather, a method of wet-coagulating the PU resin by impregnating a fiber sheet with an organic solvent solution of the PU resin and then immersing the fiber sheet in a non-solvent for the PU resin (e.g., water or an organic solvent) is generally used. For example, the following patent document 1 uses an organic solvent-based PU resin, which uses N,N-dimethylformamide as a solvent for the PU resin, i.e., an organic solvent. However, in general, organic solvents are highly harmful to the human body and the environment, and therefore, for the manufacture of artificial leather, a method that does not use organic solvents is strongly required.
[0004] In the following patent document 2, a method of using a water-dispersed PU resin dispersion obtained by dispersing PU resin in water to replace the conventional organic solvent-based PU resin is studied, but the sheet-like object obtained by impregnating the fiber sheet with the water-dispersed PU resin dispersion and solidifying the PU resin has the problem that the texture is easy to harden. One of the main reasons is that there is a difference in the solidification method of the two. That is, the solidification method of the organic solvent-based PU resin dispersion is a "wet solidification method" in which the PU molecules are precipitated and solidified by replacing the organic solvent in which the PU molecules are dissolved with water. If viewed from the PU film, a porous film with low density is formed. Therefore, when the PU resin is impregnated into the fiber sheet and solidified, the bonding part between the fiber and the PU resin also exists in a point shape, and the PU resin is easy to present a porous structure, so it becomes a soft sheet-like object. On the other hand, the water-dispersed PU resin is mainly a "dry heat solidification method" in which the hydration state of the PU molecules dispersed in water collapses by heating, and the PU molecules are solidified by aggregating each other, and the resulting PU film structure becomes a high-density non-porous film. Therefore, the bonding between the fiber and the PU resin becomes dense, and the interlaced part of the fiber is firmly controlled, so the texture becomes hard. Based on the knowledge that the technology of making the structure of the PU resin in the sheet into a porous structure in order to improve the texture by applying the water-dispersible PU resin, that is, to suppress the control of the fiber interlaced points by the PU resin, the following contents are disclosed: a sheet manufacturing method characterized by applying a PU resin dispersion containing a water-dispersible PU resin, a foaming agent and an anionic surfactant and / or a zwitterionic surfactant to a fiber sheet, thereby being able to manufacture a sheet having a porous structure of the PU resin inside the sheet regardless of the type of the foaming agent and the PU, a beautiful surface quality with excellent fiber density, softness and excellent rebound feeling, and good texture.
[0005] However, in the sheet obtained by the method described in Patent Document 2, the gaps between the ultrafine fiber bundles and the PU resin become larger (porous structure of the PU resin), and the strong adhesion of the PU resin to the ultrafine fiber bundles is inhibited. As a result, although a softening of the texture is observed, the cross-sectional PU resin area ratio is still high. Not only is the dispersibility of the PU resin insufficient, but the dispersibility of single fibers has not been studied.
[0006] In addition, in the following patent document 3, in order to provide a sheet-like article and a method for preparing the same, which has a uniform feel that is not inferior to artificial leather using an organic solvent-based PU resin, a beautiful surface quality and a good texture, and further, in order to provide a sheet-like article and a method for preparing the same, which has a bending wrinkle recovery and softness similar to artificial leather using an organic solvent-based PU resin by using a water-dispersible PU resin to achieve a porous structure of the PU resin, and has a softness and a softness that are similar to those of artificial leather using an organic solvent-based PU resin, the following is disclosed as a solution: a sheet-like article, which is formed by giving a polymer elastomer (such as a water-dispersible PU resin) having a hydrophilic group as a binder to a fiber sheet formed by ultrafine fibers and / or ultrafine fiber bundles, wherein in a cross section obtained by cutting the aforementioned sheet along the thickness direction, among the aforementioned polymer elastomer observed in the cut surface, independently having 50μm 2 The proportion of the above cross-sectional area is 0.1% or more and 5.0% or less relative to the area of the artificial leather cross section in the observation field. In addition, as a method for producing a sheet-like product formed by applying a polymer elastic body having a hydrophilic group as a binder to a fiber sheet formed of ultrafine fibers, a dispersion containing the polymer elastic body and a thickener is applied to the fiber sheet, and the polymer elastic body is coagulated in hot water at a temperature of 50 to 100° C. The article states that as a thickener, guar gum or the like having high thixotropy at a low concentration is used. If the dispersion is thixotropic, the viscosity can be reduced by applying a force by stirring, etc., and the dispersion can be uniformly impregnated into the fiber sheet. Furthermore, by allowing the dispersion to stand in advance after applying a force, the viscosity is restored to the original state, so that the dispersion impregnated into the fiber sheet is difficult to fall off from the fiber sheet.
[0007] However, in the sheet obtained by the method described in Patent Document 3, the size of the water-dispersible PU resin is controlled (the PU resin blocks are miniaturized). As a result, although resin shedding, texture, and appearance quality are slightly improved, the cross-sectional PU resin area ratio is high and the dispersibility of the PU resin is insufficient. In addition, the dispersibility of single fibers has not been studied.
[0008] In the following patent document 4, for the purpose of providing an artificial leather substrate having various mechanical properties, softness, excellent texture and raw material feel, and light weight, a substrate for artificial leather formed by a three-dimensional entangled nonwoven fabric and a polymer elastomer is proposed, which satisfies the following conditions (1): the polymer elastomer is discontinuously present on the surface of the fibers forming the three-dimensional entangled nonwoven fabric; condition (2): the removal of less than 350 μm in the cross section parallel to the thickness direction of the artificial leather substrate 2 The average area of the inscribed circle between the gaps after the inscribed circle area between the gaps is 1250μm 2Below; and, condition (3): the area of the inscribed circle between the gaps in the cross section parallel to the thickness direction of the artificial leather substrate is 350 to 3000 μm 2 The number of inscribed circles between the gaps is more than 85% relative to the number of inscribed circles between all gaps. The artificial leather substrate is obtained by undergoing a process of impregnating a three-dimensional entangled nonwoven fabric with a water-dispersible PU resin dispersion added with polyvinyl alcohol (hereinafter also referred to as PVA) resin, and solidifying it to form a high molecular weight elastic body. It is said that the following artificial leather substrate can be obtained in patent document 4, wherein the high molecular weight elastic body and the fiber have a certain demolding structure and are discontinuously present on the fiber surface, and the PU resin is evenly dispersed inside, so that the gaps between the fibers are evenly distributed. The artificial leather substrate can be used for sports shoes, etc., has excellent mechanical properties, is soft and lightweight, and has a raw material feel with excellent texture.
[0009] However, in the artificial leather substrate obtained by the method described in Patent Document 4, although the dispersibility of the water-dispersible PU resin is improved, the softness and lightness are observed, but the dispersibility of the single fiber is not good and the compactness is lacking. In addition, the artificial leather substrate described in Patent Document 4 is mainly used for "SMOOTH" artificial leather with a grainy appearance.
[0010] In the following patent document 5, for the purpose of providing a sheet-like article, especially a leather-like sheet-like article having a good surface touch for a long time and excellent color rendering and appearance quality, and a method for producing the same, a sheet-like article is proposed, wherein a fiber sheet composed of ultrafine fibers having an average single fiber diameter of 0.3 to 7 μm contains a polymer elastomer inside, and the surface has upright hairs. For the upright hair fibers that are within 0.2 μm from the surface of the aforementioned sheet-like article in the thickness direction, the average value of the shortest fiber-to-fiber distance between one of 100 randomly selected fibers and the nearest upright hair fibers is 10 to 30 μm, and the standard deviation of the fiber-to-fiber distance between the 100 randomly selected fibers and 20 surrounding upright hair fibers selected in order of the distance from the one of the 100 randomly selected fibers is less than 10. The sheet is obtained by the following steps: step 1: a step of removing the sea component of a fiber sheet containing sea-island type fibers to reveal ultrafine fibers; step 2: a step of subjecting the ultrafine fibers of the fiber sheet containing ultrafine fibers to an alkali reduction treatment; step 3: a step of imparting a polymer elastomer to the obtained fiber sheet after the above steps 1 and 2; and step 4: a step of cutting the obtained sheet in half along the thickness direction after the above step 3, and subjecting at least one side of the sheet obtained by cutting in half to a raising treatment. Patent document 5 states that: It is preferred to perform a treatment to uniformly disperse the ultrafine fibers after the alkali reduction treatment of the ultrafine fibers. The treatment to uniformly disperse the ultrafine fibers includes the following methods: a method of spraying the fiber sheet after alkali reduction with water; a method of immersing the fiber sheet in water and dispersing it by contacting it with the water flow of a vibrating cleaner or the like; a method of dispersing it by contacting it with the water flow of a water jet punch, etc. By performing these treatments to uniformly disperse the ultrafine fibers, the looseness of the ultrafine fibers becomes uniform, and by using fibers with good color rendering properties and an average single fiber diameter of 0.3 to 7 μm, the following sheet-like material can be obtained: the surface feel is not temporarily improved by adding chemical reagents, and in particular, the long-term dispersion state of the upright hairs is good, and the sheet has a good surface feel (no rough feel), uniform upright hairs, beautiful appearance quality, and excellent color rendering properties.
[0011] However, in the process for uniformly dispersing the ultrafine fibers as described in Patent Document 5, i.e., dispersing them by contacting with a water flow of a vibrating washer or the like, the fiber dispersibility is insufficient, and the dispersibility of the PU resin is also poor. Therefore, the dense feeling and wet feeling are insufficient, and the texture (softness and hardness value) is unclear.
[0012] As described above, in the prior art, various attempts have been made to provide artificial leathers having excellent texture (hardness value), density (dispersion of fiber bundles) and wetness (appropriate size of PU resin blocks) by improving the dispersion of fibers and the dispersion of PU resin for artificial leathers obtained by impregnating fiber sheets using sea-island type fibers with PU resins. However, there is a trade-off relationship between texture (hardness value), density and wetness (appropriate size of PU resin blocks). The current situation is that artificial leathers and methods for producing the same leathers have not yet been realized that can simultaneously meet the requirements of texture (hardness value), density (dispersion of fiber bundles) and wetness (appropriate size of PU resin blocks).
[0013] Prior art literature
[0014] Patent Literature
[0015] Patent Document 1: Japanese Patent No. 4089324
[0016] Patent Document 2: Japanese Patent Application Publication No. 2014-25165
[0017] Patent Document 3: International Publication No. 2015 / 129602
[0018] Patent Document 4: Japanese Patent Application Publication No. 2017-8478
[0019] Patent Document 5: Japanese Patent Application Publication No. 2015-161040 Summary of the invention
[0020] Problem that the invention aims to solve
[0021] In view of the problems of the above-mentioned prior art, the problem to be solved by the present invention is to provide artificial leather and a method for producing the same which has low harmfulness to the human body and the environment and which has a satisfactory balance in texture (softness and hardness value), density (dispersion of fiber bundles) and moistness (appropriate size of PU resin blocks).
[0022] Solutions for solving problems
[0023] The present inventors conducted intensive studies and repeated experiments to solve the above-mentioned problems, and unexpectedly found that artificial leather having the following characteristics can solve the problems, thereby completing the present invention.
[0024] That is, the present invention is as follows.
[0025] [1] An artificial leather, characterized in that it is an artificial leather comprising a fiber sheet and a polyurethane resin, the fiber sheet comprising at least a fiber layer (A), the fiber layer (A) constituting a first outer surface of the artificial leather, and the k-neighbor distance ratio value (k=9, radius r=20 μm) between single fiber cross sections constituting the fiber layer (A) in a thickness direction section of the artificial leather is greater than 10% and less than 80%, and the cross-sectional polyurethane resin area ratio in the thickness direction section of the aforementioned fiber layer (A) is greater than 10% and less than 30%, and the standard deviation of the cross-sectional polyurethane resin area ratio in the thickness direction section of the aforementioned fiber layer (A) is less than 25%.
[0026] [2] The artificial leather according to the above-mentioned [1], wherein, in the three-dimensional image of the aforementioned fiber layer (A) based on X-ray CT, the diameter of the largest sphere entering the space obtained by removing the fibers constituting the fiber layer (A) and the aforementioned polyurethane resin, that is, the average value of the spatial dimension in the thickness direction of the fiber layer (A) (average spatial dimension) is greater than 5 μm and less than 35 μm.
[0027] [3] The artificial leather according to [1] or [2], wherein the fiber sheet has a two-layer structure consisting of a fiber layer (A) constituting the first outer surface and a loose cloth and / or a fiber layer (B) in contact with the fiber layer (A).
[0028] [4] The artificial leather according to any one of [1] to [3], wherein the average diameter of single fibers constituting the fiber layer (A) is 1.0 μm or more and 8.0 μm or less.
[0029] [5] The artificial leather according to any one of [1] to [4], wherein the polyurethane resin is a water-dispersible polyurethane resin.
[0030] [6] The artificial leather according to any one of [1] to [5], wherein the adhesion rate of the polyurethane resin to the fiber sheet is 15% by mass or more and 50% by mass or less.
[0031] [7] The artificial leather according to any one of [1] to [6], wherein the softness / hardness value is 28 cm or less.
[0032] [8] The artificial leather according to any one of [1] to [7], wherein the fiber sheet is made of polyester fibers.
[0033] [9] The artificial leather according to any one of [1] to [8], wherein the sense of density is 4.0 or higher.
[0034]
[10] A method for producing artificial leather according to any one of [1] to [9], comprising the following steps:
[0035] The process of forming a fiber web with sea-island staple fibers, and then subjecting the fiber sheet obtained thereto to a sea-removal treatment to obtain a fiber sheet in which single fibers of the island component are exposed; and
[0036] A step of subjecting the obtained fiber sheet to a water jet dispersion treatment to obtain a fiber sheet in which single fibers are dispersed.
[0037]
[11] The manufacturing method according to
[10] , further comprising the following steps:
[0038] The process of impregnating the fiber sheet in which the single fibers are dispersed with a water-dispersible polyurethane resin dispersion containing hot water-soluble resin particles, and then heating the polyurethane resin to adhere the polyurethane resin to obtain a sheet-like object filled with the polyurethane resin; and
[0039] A step of removing the hot water-soluble resin fine particles from the obtained sheet-like product using hot water.
[0040]
[12] The production method according to
[10] or
[11] , wherein the hot water-soluble resin fine particles are polyvinyl alcohol resin.
[0041]
[13] A manufacturing method according to any one of
[10] to
[12] above, wherein the water flow dispersion treatment is carried out using a plurality of nozzles having a nozzle hole spacing of less than 1.0 mm and a nozzle hole diameter of not less than 0.05 mm and not more than 0.30 mm.
[0042]
[14] The production method according to any one of
[10] to
[13] above, wherein the water flow dispersion treatment is performed using a plurality of nozzles that eject water flows with a turbulent flow of 10% or more.
[0043]
[15] The production method according to any one of
[11] to
[14] , wherein the solid content concentration of the aqueous polyurethane resin dispersion is 10% by weight or more and 35% by weight or less.
[0044]
[16] The production method according to any one of
[11] to
[15] , wherein the content of the hot water-soluble resin microparticles in the water-dispersible polyurethane resin dispersion is 1% by weight or more and 20% by weight or less.
[0045] Effects of the Invention
[0046] The artificial leather of the present invention has excellent texture (hardness / softness value), compactness (dispersion of fiber bundles) and moistness (appropriate size of polyurethane resin blocks), and therefore can be used as surface materials or interior materials for sheets for interior decoration, automobiles, aircraft, trains, etc., clothing products, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a conceptual diagram showing an example of the structure of the artificial leather of symbol 1. In addition, the loose cloth of symbol 11 and the fiber layer (B) of symbol 13 are optional, so the artificial leather of this embodiment has a single layer of the fiber layer (A) of symbol 12, a two-layer situation of the fiber layer (A) and loose cloth or the fiber layer (B), and a three-layer situation of the fiber layer (A), loose cloth, and fiber layer (B).
[0048] Figure 2 This is a conceptual diagram for explaining a method for calculating the average diameter of fibers constituting the fiber layer (A).
[0049] Figure 3 It is a conceptual diagram illustrating the single fiber cross-section k neighbor distance ratio value (%) in the thickness direction section starting from the fiber layer (A), the cross-sectional PU resin area ratio, the average diameter of the single fiber, the surface PU resin area ratio in the first outer surface, and the spatial dimensions of the respective sample sampling locations.
[0050] Figure 4 This is an image showing a state where each single fiber cross section within a predetermined image area is manually marked in order to obtain a single fiber cross section k-neighbor distance ratio value (%) in a thickness direction cross section.
[0051] Figure 5 This is a conceptual diagram for explaining a method for calculating a value (%) of a k-neighbor distance ratio of a single fiber cross section in a thickness direction cross section.
[0052] Figure 6 This is a conceptual diagram for explaining the calculation method of the cross-sectional or surface PU resin area ratio and its standard deviation.
[0053] Figure 7 This is a graph comparing the cross-sectional PU resin area ratio (%) and its standard deviation for Examples and Comparative Examples.
[0054] Figure 8 This is a conceptual diagram showing the nozzle hole interval when the nozzle holes of the nozzle used in the water flow dispersion treatment are in one row or two or more rows. DETAILED DESCRIPTION
[0055] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to the embodiments. In addition, various values of the present application are values obtained by the method described in the [Examples] of the present application or by those skilled in the art who consider the method equivalent thereto unless otherwise specified.
[0056] <Artificial leather>
[0057] One embodiment of the present invention is an artificial leather, characterized in that it is an artificial leather comprising a fiber sheet and a PU resin, the fiber sheet comprising at least a fiber layer (A), the fiber layer (A) constituting a first outer surface of the artificial leather, and the k-neighbor distance ratio value (k=9, radius r=20 μm) between single fiber cross sections constituting the fiber layer (A) in a thickness direction section of the artificial leather is greater than 10% and less than 80%, and the cross-sectional polyurethane resin area ratio in the thickness direction section of the aforementioned fiber layer (A) is greater than 10% and less than 30%, and the standard deviation of the cross-sectional polyurethane resin area ratio in the thickness direction section of the aforementioned fiber layer (A) is less than 25%.
[0058] In this specification, "artificial leather" means: according to the Household Goods Quality Display Act, "a substrate made of a special non-woven fabric (mainly composed of a fiber layer having a random three-dimensional structure and impregnated with a PU resin or a polymer elastomer having similar flexibility)". In addition, in the definition of JIS-6601, artificial leather is classified according to its appearance into "SMOOTH" having a grain-like appearance of leather and "NAP" having an appearance of suede, velvet, etc. of leather. The artificial leather of the present embodiment is classified as "NAP" (i.e., suede-like artificial leather having a raised appearance). The suede-like appearance can be formed by polishing (raising) the outer surface of the fiber layer (A) (i.e., the surface that becomes the first outer surface of the artificial leather) using sandpaper or the like. In addition, in this specification, the first outer surface of the artificial leather refers to the surface that is exposed to the outside when the artificial leather is used (for example, in the case of chair use, it is the surface on the side that comes into contact with the human body) (refer to Figure 1 , Figure 3 ) In one embodiment, in the case of suede-like artificial leather, the first outer surface is napped or raised by polishing or the like.
[0059] In this specification, unless otherwise specified, the term "fiber web" refers to the state before interweaving of short fibers, the term "fiber sheet" refers to the state after interweaving to before PU resin filling, the term "sheet" refers to the state after PU resin filling to before dyeing and finishing, and the term "artificial leather" refers to the state of the product after dyeing and finishing. In addition, the term "non-woven fabric" includes "fiber web", "fiber sheet", "sheet", "artificial leather", and the term "fibrous substrate" refers to the term "non-woven fabric" and also includes woven / knitted fabrics, etc.
[0060] [k-neighbor distance ratio value between single fiber cross sections constituting the fiber layer (A) (k=9, radius r=20 μm)]
[0061] One feature of the present embodiment is that the k-nearest neighbor distance ratio value (k=9, radius r=20 μm) between the cross sections of the single fibers constituting the fiber layer (A) in the thickness direction cross section of the artificial leather is 10% or more and 80% or less. The k-nearest neighbor distance ratio value (k=9, radius r=20 μm) is an indicator of the density of the single fibers.
[0062] The measurement method is described below. The k nearest neighbor method refers to a method of determining the boundary by taking k single fiber cross sections close to any single fiber cross section and using the radius close to the kth one in the Euclidean distance (i.e., the square root of the sum of the squares of the distances in the X direction and the Y direction (= the shortest distance)). In this embodiment, an SEM image is taken to determine whether there is a single fiber cross section close to the k=9th one within a distance of 20 μm from the approximate center of any single fiber cross section. For all single fiber cross sections in one SEM image, the presence or absence of such a cross section is determined, and the ratio value (%) of the k=9 nearest neighbor distance of the single fiber cross section is calculated using the following formula:
[0063] The neighbor distance ratio value (%) of a single fiber section (k=9) = {(the number of single fiber sections close to the k=9th single fiber section within a distance of 20 μm from the approximate center of the single fiber section) / (the total number of single fiber sections in one SEM image)}×100.
[0064] If the k-neighbor distance ratio value (k=9, radius r=20μm) between the single fiber cross sections constituting the fiber layer (A) in the thickness direction section of the artificial leather is 10% or more, the single fibers exist in a moderately dispersed state, and as a result, the PU resin blocks of the fiber layer (A) are also moderately dispersed. If the artificial leather is touched with fingertips, the moderately dispersed PU resin blocks are touched, and thus, the moist feeling (appropriate size of the PU resin blocks) can be satisfied. On the other hand, if the k-neighbor distance ratio value (k=9, radius r=20μm) is 80% or less, the single fibers are moderately aggregated, and thus, the dense feeling (dispersion of the fiber bundle) is high, presenting a smooth touch. The k-neighbor distance ratio value (k=9, radius r=20μm) is preferably 20% or more and 70% or less, and more preferably 30% or more and 60% or less.
[0065] As described later, after forming a fiber web with island staple fibers, and then performing a needle punching process, the fiber sheet thus obtained is subjected to a sea removal process to obtain a fiber sheet in which single fibers of the island component are exposed, and then a water flow dispersion process is performed on the obtained fiber sheet to obtain a fiber sheet in which single fibers are dispersed, thereby enabling the k-neighbor distance ratio value (k=9, radius r=20μm) to be controlled within a range of less than 80%. As the water flow dispersion process, it is preferred to use a plurality of nozzles with nozzle holes spaced at intervals of less than 1.00mm to spray high-pressure water. Figure 8 As shown in FIG. 1 , the nozzle hole spacing refers to the distance in the nozzle width direction between a nozzle hole and the nozzle hole closest to the nozzle hole in the nozzle width direction (when there are two or more rows of nozzle holes, the same applies to the case of one row). By setting the nozzle hole spacing to 1.00 mm or less, it is possible to spray water streams with dense spacing on the fiber sheet, and by dispersing the single fibers in the state of single fiber bundles, it is easy to improve the dense feeling and wet feeling. In addition, the water flow track caused by the water flow dispersion treatment on the fiber sheet surface is not easy to be conspicuous. The nozzle hole spacing is preferably 0.60 mm or less, and more preferably 0.30 mm or less.
[0066] In addition, the number of rows of nozzle holes opened in the width direction of the water flow dispersion treatment device may be one row or two or more rows. When performing water flow dispersion treatment, from the viewpoint of maintaining the uniformity and morphological stability of the fiber sheet, the water input to the fiber sheet during the water flow dispersion treatment is usually removed, and dehydration is performed from the opposite side of the water flow dispersion treatment surface by a suction method or the like. In this case, for example, when the nozzle hole interval is narrowed under the condition that the number of nozzle hole rows is one row, the dehydration capacity is insufficient relative to the amount of water input, and as a result, the uniformity and morphological stability of the fiber sheet may be deteriorated. In contrast, by setting the number of rows to multiple rows and widening the nozzle hole interval of each nozzle hole row, thereby reducing the amount of water input per nozzle hole row, it is easy to present a balance between the amount of water input and the dehydration capacity, so this is a preferred method. For example, when poor dehydration occurs in a row of nozzles with a nozzle hole interval of 0.30 mm, if two rows of nozzles with a nozzle hole interval of 0.60 mm are set in one row, and the second row is configured with a nozzle hole row with a phase difference of 0.30 mm and a nozzle interval of 0.60 mm relative to the first row, the water flow trajectory (nozzle hole interval) reaches 0.30 mm, and the effect of improving poor dehydration can be obtained. In addition, when the nozzle hole interval is widened and multiple rows are set, it is easy to operate the nozzle, so it is also preferred. From the viewpoint of making it easy to evenly disperse the single fibers, making the water flow trajectory less noticeable, and improving the dense feeling and moist feeling, the nozzle hole interval (water flow trajectory) is preferably equidistant.
[0067] From the viewpoint of dehydration performance, for example, when the number of nozzle hole rows is plural, the distance between nozzle hole rows is preferably set to a distance corresponding to the interval between nozzle holes in one row of nozzles.
[0068] From the viewpoint of easily obtaining high single fiber dispersion and making the water flow trajectory less conspicuous, thereby not causing excessive water input and easily achieving a balance with the dehydration capacity, the aperture diameter of the high-pressure water jet nozzle hole in the water flow dispersion treatment is preferably greater than 0.05 mm and less than 0.30 mm, more preferably greater than 0.05 mm and less than 0.20 mm, and further preferably greater than 0.08 mm and less than 0.13 mm.
[0069] In addition, it is preferred to spray under the condition that the water pressure of the water flow dispersion treatment is 1.0 to 10.0 MPa. By setting the water pressure of the water flow dispersion treatment to 1.0 MPa or more, it is easy to disperse the single fibers in the single fiber bundle state, and by setting the water pressure of the water flow dispersion treatment to 10.0 MPa or less, the short fiber bundle will not be over-dispersed, so it is easy to control the k nearest neighbor distance ratio value to 10% or more and 80% or less. In addition, it is easy to disperse the single fibers in the single fiber bundle state, and the water flow trajectory is not easy to be conspicuous. When the water pressure of the water flow dispersion treatment is high, the water flow sometimes penetrates the fiber sheet and is not used as energy to disperse the single fiber bundle. Compared with the case of treatment under low water pressure, the dispersion effect of the single fiber bundle is sometimes reduced. In addition, when the water pressure of the water flow dispersion treatment is high, there is a tendency for the fiber sheet to become high-density and the texture (softness and hardness value) to deteriorate. The water pressure of the dispersion treatment is more preferably 1.5 to 7.0 MPa, and more preferably 2.0 to 4.5 MPa.
[0070] As the shape of the water flow ejected from the nozzle hole, it is also preferred to use a plurality of nozzles that eject water flow with a turbulence of 10% or more. Turbulence is an indicator of the diameter variation of the water flow. From the perspective of being able to convert the energy of the water flow into fiber dispersion with good efficiency, the turbulence is preferably 12% or more, and more preferably 15% or more. The turbulence is calculated as follows: the average diameter of the water flow within the range of 25mm to 35mm from the nozzle hole is set as W, the standard deviation of the average diameter is set as σ, and it is calculated by the following formula:
[0071] Turbulence (%)=σ(mm) / W(mm)×100.
[0072] The mechanism of dispersion of a single fiber bundle based on turbulence is not yet clear, but the inventors of the present invention believe that, in the case of large turbulence, the water flow energy is easily dispersed in multiple directions toward the horizontal direction in addition to being dispersed in the vertical direction of the fiber sheet, compared with the case of small turbulence, so that the water flow energy can be converted into dispersed energy of the single fiber bundle with good efficiency, and thus the dispersion effect becomes higher. As an example, it can be considered that the water flow energy that is wasted by passing through the fiber sheet under high water pressure is easily used as dispersion energy.
[0073] Furthermore, it is preferable to make the high-pressure water jet nozzle perform circular motion or reciprocating motion perpendicular to the process advancing direction (machine direction) in order to promote the dispersion of single fibers and improve the dense feeling and moist feeling.
[0074] Based on the dispersion effect of the single fiber bundle, from the perspective of flow guidance before water flow dispersion treatment and process passability during water flow dispersion treatment, the distance from the high-pressure water jet surface to the treated object is preferably greater than 5 mm and less than 100 mm, more preferably greater than 10 mm and less than 60 mm, and further preferably greater than 20 mm and less than 40 mm.
[0075] [Cross-sectional PU resin area ratio in the cross section in the thickness direction of the fiber layer (A) and its standard deviation]
[0076] In the artificial leather of this embodiment, the cross-sectional PU resin area ratio in the thickness direction cross section of the fiber layer (A) is 10% to 30%, and the standard deviation of the cross-sectional PU resin area ratio is 25% or less.
[0077] If the cross-sectional PU resin area ratio exceeds 30%, the PU resin adhesion rate becomes too high, and the rubber texture of the artificial leather becomes stronger. At this time, the softness decreases and the texture becomes hard. When there is no loose coarse cloth in the artificial leather, the cross-sectional PU resin area ratio is 10% or more from the viewpoint of easily obtaining sufficient mechanical properties in the plane direction. The cross-sectional PU resin area ratio is preferably 15% or more and 30% or less, more preferably 15% or more and 28% or less, and further preferably 15% or more and 26% or less.
[0078] The cross-sectional PU resin area ratio and the aforementioned k-neighbor distance ratio value (k=9, radius r=20μm) are both indicators of the texture (hardness and softness value) described below. For example, when the k-neighbor distance ratio value (k=9, radius r=20μm) exceeds 80%, there are excessive single fiber bundles. On the other hand, the water-dispersible PU resin has a great tendency to adhere when attached to single fibers and single fiber bundles. In other words, in the presence of excessive single fiber bundles with a k-neighbor distance ratio value of more than 80%, if the cross-sectional PU resin area ratio is more than 10%, the PU resin blocks aggregate and adhere to the single fiber bundles, and thus the texture (hardness and softness value) deteriorates. If the k-neighbor distance ratio value (k=9, radius r=20μm) is more than 10% and less than 80%, and further, the cross-sectional PU resin area ratio is more than 10% and less than 30%, the texture (hardness and softness value) becomes less than 28cm.
[0079] As described later (ref. Figure 6), the cross-sectional PU resin area ratio refers to: the PU resin in the SEM image is binarized as a black part, and the area ratio of the PU resin relative to each partition is calculated by the differentiation method based on the obtained binary image, and the cross-sectional PU resin area ratio (%) is averaged for all partitions to obtain the area ratio, and its standard deviation is an indicator of the deviation compared with the average for all partitions. If the standard deviation of the cross-sectional PU resin area ratio is less than 25%, the distribution of the size of the PU resin blocks can be controlled, and therefore, the deviation of the texture (softness and hardness value) becomes smaller. The standard deviation of the cross-sectional PU resin area ratio is preferably less than 25%, more preferably less than 22%, and further preferably less than 20%. The lower limit of the standard deviation of the cross-sectional PU resin area ratio is not particularly limited, as long as it is greater than 0%.
[0080] As described later, for example, by impregnating a water-dispersible PU resin dispersion containing hot water-soluble resin particles (such as PVA resin particles), and then heating the PU resin to adhere the PU resin to obtain a sheet-like object filled with PU resin, the cross-sectional PU resin area ratio can be controlled to be 10% or more and 30% or less. In addition, after forming a fiber web with sea-island short fibers, and then performing a needle punching treatment, the fiber sheet obtained thereby is subjected to a sea-removing treatment to obtain a fiber sheet in which single fibers of the island component are exposed, and then performing the aforementioned water flow dispersion treatment on the obtained fiber sheet to obtain a fiber sheet in which single fibers are dispersed, the PU resin attached to the fiber is also dispersed as the single fibers are dispersed, and as a result, the standard deviation of the cross-sectional PU resin area ratio can be controlled to be 25% or less.
[0081] [Average space size]
[0082] In the artificial leather of the present embodiment, in the three-dimensional image based on X-ray CT of the aforementioned fiber layer (A), the diameter of the largest ball entering the space after removing the fibers constituting the fiber layer (A) and the aforementioned PU resin, that is, the average value of the spatial dimension in the thickness direction of the artificial leather (average spatial dimension) is preferably greater than 5 μm and less than 35 μm.
[0083] As described later, the average spatial size refers to the average value of the diameter (μm) of the largest ball in the space after removing the single fibers and PU resin constituting the fiber layer (A) by taking a three-dimensional image of the fiber layer (A) using X-ray CT. The average spatial size is an indicator of the dispersion state of the structure formed by the fiber and PU resin block in the fiber layer (A) of the artificial leather. When the average spatial size is large, it means that the fiber and the PU resin block exist in close contact. If the average spatial size is in the range of 5μm or more and 35μm or less, the fiber and the PU resin are moderately dispersed, so the texture (softness and hardness value) is easy to become less than 28cm. As described later, for example, by implementing a process in which a fiber sheet dispersed with single fibers is impregnated with a water-dispersible PU resin dispersion containing hot water-soluble resin particles (such as PVA resin particles), and then the PU resin is adhered by heating to obtain a fiber sheet filled with PU resin, the average spatial size of the artificial leather as the final product can be controlled to be 5μm or more and 35μm or less. The average space size is more preferably 5 μm or more and 25 μm or less, and further preferably 5 μm or more and 13 μm or less.
[0084] [PU resin adhesion rate to fiber sheet]
[0085] In the artificial leather of the present embodiment, the adhesion rate of the PU resin to the fiber sheet is preferably 15% by mass or more and 50% by mass or less, more preferably 22% by mass or more and 45% by mass or less, and further preferably 26% by mass or more and 40% by mass or less. The ratio of the PU resin to the fiber sheet will affect the controllability of the aforementioned cross-sectional PU resin area ratio and the average spatial size. When the ratio of the PU resin is low, there is a tendency for the cross-sectional PU resin area ratio to be low and the average spatial size to be large. On the other hand, when the ratio of the PU resin is high, there is a tendency for the cross-sectional PU resin area ratio to be high and the average spatial size to be small. If the ratio of the PU resin to the fiber sheet is 15% by mass or more, it is easy to use the PU resin to control the fibers well, and it is easy to obtain mechanical strength such as wear resistance that meets market demand. On the other hand, if the ratio of the PU resin to the fiber sheet is 50% by mass or less, a soft texture is easily obtained.
[0086] [Polyurethane (PU) resin]
[0087] The PU resin is preferably obtained by reacting a polymer diol with an organic diisocyanate and a chain extender.
[0088] As the polymer diol, for example, diols of polycarbonate, polyester, polyether, silicone, fluorine, etc. can be used, and copolymers obtained by combining two or more of them can also be used. From the viewpoint of hydrolysis resistance, diols of polycarbonate or polyether or their combination are preferably used. In addition, from the viewpoint of light resistance and heat resistance, diols of polycarbonate, polyester or their combination are preferably used. Furthermore, from the viewpoint of cost competitiveness, diols of polyether, polyester or their combination are preferably used.
[0089] The polycarbonate diol can be produced by, for example, a transesterification reaction of an alkylene glycol with a carbonate, a reaction of phosgene or a chloroformate with an alkylene glycol.
[0090] Examples of the alkylene glycol include straight-chain alkylene glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, and 1,10-decanediol; branched-chain alkylene glycols such as neopentyl glycol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, and 2-methyl-1,8-octanediol; alicyclic diols such as 1,4-cyclohexanediol; and aromatic diols such as bisphenol A. These can be used alone or in combination of two or more.
[0091] Examples of the polyester diol include polyester diols obtained by condensing various low-molecular-weight polyols and polybasic acids.
[0092] As the low molecular weight polyol, for example, one or more selected from ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,2-dimethyl-1,3-propylene glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,8-octanediol, diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, cyclohexane-1,4-diol, and cyclohexane-1,4-dimethanol can be used. In addition, adducts obtained by adding various alkylene oxides to bisphenol A can also be used.
[0093] Examples of the polybasic acid include one or more selected from the group consisting of succinic acid, maleic acid, adipic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, phthalic acid, isophthalic acid, terephthalic acid, and hexahydroisophthalic acid.
[0094] Examples of the polyether diol include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and copolymeric glycols obtained by combining these.
[0095] The number average molecular weight of the polymer diol is preferably 500 to 4000. By setting the number average molecular weight to 500 or more, more preferably 1500 or more, the texture can be prevented from becoming hard. In addition, by setting the number average molecular weight to 4000 or less, more preferably 3000 or less, the strength of the PU resin can be well maintained.
[0096] As organic diisocyanates, for example, aliphatic diisocyanates such as hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, and xylylene diisocyanate; aromatic diisocyanates such as diphenylmethane diisocyanate and toluene diisocyanate can be cited, and they can also be used in combination. Among them, from the viewpoint of light resistance, aliphatic diisocyanates such as hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, and isophorone diisocyanate are preferably used.
[0097] As the chain extender, an amine-based chain extender such as ethylenediamine and methylenedianiline, or a diol-based chain extender such as ethylene glycol can be used. In addition, a polyamine obtained by reacting a polyisocyanate with water can also be used as a chain extender.
[0098] In addition, the PU resin can be used in the form of a solvent-type PU resin obtained by dissolving the PU resin in an organic solvent such as N,N-dimethylformamide, a water-dispersible PU resin in which the PU resin is emulsified with an emulsifier and dispersed in water, etc. Among them, from the perspective of easily filling the PU resin into the fiber sheet in a fine form, easily obtaining the required performance of artificial leather such as texture and mechanical properties even with a small amount of attachment, and reducing the environmental burden without using an organic solvent, a water-dispersible PU resin is preferred. That is, with respect to the water-dispersible PU resin, since the PU resin can be impregnated into the fiber sheet in the form of a dispersion obtained by dispersing in a desired particle size (hereinafter also referred to as a PU resin dispersion), the filling form of the PU resin in the fiber sheet can be well controlled by controlling the particle size.
[0099] As the water-dispersible PU resin, a self-emulsifying PU resin containing a hydrophilic group in the PU molecule, a forced emulsifying PU resin obtained by emulsifying the PU resin with an external emulsifier, or the like can be used.
[0100] In the water-dispersible PU resin, a cross-linking agent can be used in combination for the purpose of improving durability such as resistance to moisture and heat, abrasion resistance, and hydrolysis resistance. In order to improve the durability during liquid flow dyeing, inhibit the shedding of fibers, and obtain excellent surface quality, a cross-linking agent is preferably added. The cross-linking agent can be an external cross-linking agent added in the form of an added component relative to the PU resin, and can also be an internal cross-linking agent that pre-introduces reactive groups that can achieve a cross-linked structure into the PU resin structure.
[0101] The water-dispersible PU resin used in artificial leather usually has a cross-linked structure in order to have dyeing resistance, and therefore, tends to be difficult to dissolve in organic solvents such as N,N-dimethylformamide. Therefore, for example, when artificial leather is immersed in N,N-dimethylformamide at room temperature for 12 hours to dissolve the PU resin, when the cross section is observed using an electron microscope, as long as a resin-like substance without a fiber shape remains, it can be determined that the resin-like substance is a water-dispersible PU resin.
[0102] In a preferred embodiment, from the viewpoint of easily controlling the cross-sectional PU resin area ratio and its standard deviation, as well as the average spatial size, it is preferred that: a PU resin dispersion is used to fill the PU resin, and at this time, the average primary particle size of the PU resin in the dispersion is greater than 0.1 μm and less than 0.8 μm, more preferably greater than 0.1 μm and less than 0.6 μm, and further preferably greater than 0.2 μm and less than 0.5 μm. In addition, the average primary particle size is a value obtained by measuring the PU resin dispersion based on a laser diffraction particle size distribution measuring device ("LA-920" manufactured by Horiba, Ltd.). By making the average primary particle size of the PU resin greater than 0.1 μm, the force (i.e., bonding force) of the fibers in the fiber sheet held together by the PU resin is good, thereby, an artificial leather with excellent mechanical strength can be obtained. In addition, when the average primary particle size of the PU resin is set to 0.8 μm or less, it is advantageous in that the aggregation or coarsening of the PU resin can be suppressed and the standard deviation of the cross-sectional PU resin area ratio can be controlled to be less than 25%. By setting the average primary particle size of the PU resin in the PU resin dispersion to be greater than 0.1 μm and less than 0.8 μm, the points at which the fibers constituting the artificial leather (especially its surface layer) are held by each other are increased, and a soft texture (softness and hardness value) and excellent mechanical strength (wear resistance, etc.) can be obtained.
[0103] [Solid content concentration of PU resin dispersion]
[0104] As described later, in a typical embodiment, the PU resin is impregnated in the form of an impregnation liquid such as a solution (for example, in the case of a solvent-dissolved type) or a dispersion (for example, in the case of a water-dispersed type). For example, the solid content concentration of the water-dispersed PU resin dispersion can be 10% by weight or more and 35% by weight or less, more preferably 15 to 30% by weight, and even more preferably 15 to 25% by weight. In one embodiment, the impregnation liquid is prepared and impregnated into the fiber sheet in such a manner that the adhesion rate of the PU resin relative to 100% by weight of the fiber sheet is 15% by weight or more and 50% by weight or less.
[0105] Additives such as stabilizers (ultraviolet absorbers, antioxidants, etc.), flame retardants, antistatic agents, pigments (carbon black, etc.) can be added to the impregnation liquid containing PU resin (e.g., water-dispersible PU resin) as needed. The total amount of these additives present in the artificial leather can be, for example, 0.1 to 10.0 parts by mass, 0.2 to 8.0 parts by mass, or 0.3 to 6.0 parts by mass relative to 100 parts by mass of the PU resin. In addition, such additives will be distributed in the PU resin of the artificial leather. In this application, the values mentioned when referring to the size of the PU resin and the mass ratio relative to the fiber sheet refer to values that also include additives (when used).
[0106] [Hot-water soluble resin particles]
[0107] When the fiber sheet is filled with PU resin by impregnating the fiber sheet with an impregnation liquid containing PU resin, it is preferable to carry out the following steps: impregnating the fiber sheet with a water-dispersible PU resin dispersion containing hot water-soluble resin microparticles, and then adhering the PU resin by heating to obtain a sheet-like object filled with PU resin. In a post-process or dyeing process, the hot water-soluble resin microparticles are removed from the obtained fiber sheet using hot water, thereby partially disconnecting and making porous the continuous layer of PU resin, thereby obtaining an effect of making the adhesion state of PU resin finer.
[0108] As hot water soluble resin particles, partially saponified PVA resin particles, completely saponified PVA resin particles, etc. can be cited. Compared with partially saponified PVA resin particles, completely saponified PVA resin particles tend to be difficult to dissolve into water at room temperature (20°C), so it is preferred to use completely saponified PVA resin particles as hot water soluble resin particles. From the perspective of not being easily dissolved into water at room temperature (20°C), the saponification degree of completely saponified PVA resin particles is preferably 95 mol% or more, more preferably 98 mol% or more. In order to take into account the force of bonding and holding the fiber and the miniaturization of the attached state of the PU resin, the average particle size (size) of the hot water soluble resin particles is preferably 1 μm or more and 8 μm or less, more preferably 2 μm or more and 6 μm or less, and more preferably 2 μm or more and 4 μm or less. By setting the above-mentioned average particle size to 1 μm or more, the hot water soluble resin particles are difficult to aggregate, and by setting the above-mentioned average particle size to 8 μm or less, the hot water soluble resin particles are easy to penetrate well into the fiber sheet. As the fine particles, "NL-05" manufactured by Mitsubishi Chemical Corporation can be used. The hot water-soluble resin fine particles can be miniaturized by the method described in Japanese Patent Application Laid-Open No. 7-82384.
[0109] The content of hot water-soluble resin microparticles in the water-dispersible PU resin dispersion is preferably 1% by weight or more and 20% by weight or less, more preferably 2% by weight or more and 15% by weight or less, and further preferably 3% by weight or more and 10% by weight or less. By including 1% by weight or more of hot water-soluble resin microparticles in the water-dispersible PU resin dispersion, the dispersion of PU resin blocks is easily promoted. On the other hand, by including 20% by weight or less of hot water-soluble resin microparticles in the water-dispersible PU resin dispersion, the microparticles do not aggregate, and the stability of the dispersion is easily maintained.
[0110] In addition, in this specification, "hot water-soluble resin" means a resin which is poorly soluble in water at room temperature.
[0111] [Hot water soluble resin]
[0112] When a fiber sheet is impregnated with a water-dispersible PU resin dispersion containing hot water-soluble resin microparticles, and then the PU resin is adhered by heating to obtain a sheet-like object filled with PU resin, a process of attaching the hot water-soluble resin to the fiber sheet may be performed before the fiber sheet is impregnated with a water-dispersible PU resin dispersion containing hot water-soluble resin microparticles. As a method for attaching a hot water-soluble resin (such as a PVA resin), it can be attached by preparing an aqueous solution of a hot water-soluble resin and impregnating the aqueous solution into the fiber sheet and then drying it. In a post-process or dyeing process, the hot water-soluble resin microparticles and the hot water-soluble resin are removed from the obtained fiber sheet together using hot water, thereby obtaining the following effects: hindering the adhesion between the fiber and the PU resin, disconnecting a part of the continuous layer of the PU resin and making it porous, and making the attached state of the PU resin finer, thereby easily improving the texture of the artificial leather.
[0113] As hot water soluble resins, partially saponified PVA resins, completely saponified PVA resins, etc. can be cited. Compared with partially saponified PVA resins, completely saponified PVA resins tend to be difficult to dissolve in water at room temperature (20°C). Therefore, as hot water soluble resins, completely saponified PVA resins are preferably used. From the viewpoint of being difficult to dissolve in water at room temperature (20°C), the saponification degree of completely saponified PVA resins is preferably 95 mol% or more, more preferably 98 mol% or more. In addition, in order to improve the permeability of the hot water soluble resin aqueous solution during impregnation, the degree of polymerization is preferably 1000 or less, more preferably 700 or less.
[0114] [Fiber sheet]
[0115] like Figure 1As shown, the fiber sheet 1 includes at least a fiber layer (A) 12, and the loose cloth 11 and the fiber layer (B) 13 are optional and not essential elements. Therefore, the artificial leather of this embodiment has the following situations: a single layer of the fiber layer (A), a two-layer situation of the fiber layer (A) and the loose cloth or the fiber layer (B), and a three-layer situation of the fiber layer (A), the loose cloth and the fiber layer (B).
[0116] When the loose cloth 11 and / or the fiber layer (B) 13 are not included, as described later, the fiber layer (A) may be a layer obtained by cutting a single-layer fiber sheet filled with PU resin in half. In one embodiment, the fiber sheet is a single-layer structure without loose cloth. This is because: the productivity is improved by cutting in half.
[0117] In other embodiments, the fiber sheet has a three-layer structure and the muslin is the middle layer. For example, a three-layer structure in which a muslin 11 as a woven / knitted fabric is sandwiched between a fiber layer (A) 12 constituting the first outer surface of the artificial leather and a fiber layer (B) 13 constituting the second outer surface of the artificial leather and the fibers are interwoven between these layers is preferred in terms of dimensional stability, tensile strength, tear strength, etc. In addition, according to the three-layer structure of the fiber layer (A) and the fiber layer (B) and the muslin sandwiched by them, the fiber layer (A) and the fiber layer (B) can be designed separately, and therefore, it is preferred in that the diameter, type, etc. of the fibers constituting these layers can be freely changed in accordance with the functions and uses required for the artificial leather. For example, if ultrafine fibers are used in the fiber layer (A) and flame-retardant fibers are used in the fiber layer (B), respectively, excellent surface quality and high flame retardancy can be achieved.
[0118] When the fiber sheet includes loose cloth, from the viewpoint of the same color based on dyeing, the loose cloth as a woven / knitted fabric is preferably the same polymer system as the fiber constituting the fiber layer (A). For example, if the fiber constituting the fiber layer (A) is a polyester system, the fiber constituting the loose cloth is also preferably a polyester system, and if the fiber constituting the fiber layer (A) is a polyamide system, the fiber constituting the loose cloth is also preferably a polyamide system. The loose cloth when it is a knitted fabric is preferably a single-sided knitted fabric woven with more than 22 gauges and less than 28 gauges. When the loose cloth is a woven fabric, it can achieve higher dimensional stability and strength than a knitted fabric. The organization of the woven fabric can be a plain weave, a twill weave, a satin weave, etc., and is preferably a plain weave from the aspects of cost and interweaving processes.
[0119] The yarns constituting the woven fabric may be monofilaments or multifilaments. From the viewpoint of easily obtaining soft artificial leather, the single fiber fineness of the yarns is preferably 5.5 dtex or less. As the form of the yarns constituting the woven fabric, it is preferably a raw yarn of a multifilament of polyester, polyamide, etc.; or a material obtained by twisting a processed yarn subjected to false twisting at a twist number of 0 to 3000 T / m. The multifilament may be a common multifilament, and it is preferred to use 33dtex / 6f, 55dtex / 24f, 83dtex / 36f, 83dtex / 72f, 110dtex / 36f, 110dtex / 48f, 167dtex / 36f, 166dtex / 48f, etc. of polyester, polyamide, etc. The yarns constituting the woven fabric may be long fibers of a multifilament. From the viewpoint of obtaining an artificial leather that is soft and has excellent mechanical strength, the weaving density of the yarns in the woven fabric is preferably 30 to 150 yarns / inch, and more preferably 40 to 100 yarns / inch. In order to have good mechanical strength and a moderate texture, the weight per unit area of the woven fabric is preferably 20 to 150 g / m 2 In addition, the presence or absence of false twist processing in the woven fabric, the number of twists, the single fiber fineness of the multifilament, the weaving density, etc. not only contribute to the interweaving of the fibers constituting the fiber layer (A) and the fiber layer (B) as an optional layer, and the softness of the artificial leather, but also contribute to the mechanical properties such as stitch strength, tear strength, tensile strength elongation, and stretchability. Therefore, it can be appropriately selected according to the target physical properties and uses.
[0120] From the viewpoint of obtaining an artificial leather having a higher level of abrasion resistance, dyeability and surface quality, in the artificial leather of the present embodiment, the fiber layer (A) is preferably composed of fibers having an average diameter of 1 μm or more and 8 μm or less, more preferably 2 μm or more and 6 μm or less, and further preferably 2 μm or more and 5 μm or less. If the average diameter of the fiber is 1 μm or more, the abrasion resistance, color development based on dyeing and light fastness are good. On the other hand, if the average diameter of the fiber is 8 μm or less, the root number density of the fiber is large, and therefore, it is easy to obtain an artificial leather with a high sense of density, a smooth surface touch and better surface quality.
[0121] As the fiber forming the fiber layer constituting the artificial leather (the fiber layer (A) and the fiber layer (B) as an optional layer and the additional layer), suitable are polyester fibers such as polyethylene terephthalate, polybutylene terephthalate, and polytrimethylene terephthalate; synthetic fibers such as polyamide fibers such as nylon 6, nylon 66, and nylon 12. Among them, considering the use requiring durability such as the field of car seats, polyethylene terephthalate is preferred from the viewpoint that the fiber itself does not turn yellow even when exposed to direct sunlight for a long time and has excellent color fastness. In addition, from the viewpoint of reducing the environmental burden, as the fiber forming the fiber layer constituting the artificial leather, polyethylene terephthalate obtained by chemical recycling or material recycling, or polyethylene terephthalate obtained using raw materials derived from plants, etc. is further preferred.
[0122] In this specification, the fiber "dispersed in single fibers" means that the fiber does not form a fiber bundle such as the island component in the following sea-island type composite fiber. For example, by using ultrafine fiber-generating fibers such as sea-island type composite fibers (e.g., fibers obtained by using copolyester as the sea component and ordinary polyester as the island component), a three-dimensional interwoven body of the fiber and loose coarse cloth is made, and then the fiber is subjected to a fibrillation treatment (removing the sea component of the sea-island type composite fiber by dissolving, decomposing, etc.), and the fiber obtained exists in the fiber layer (A) in the form of a fiber bundle, and is not dispersed in single fibers. As an example, by making a sea-island type composite short fiber with a single fiber fineness of 0.2 dtex and 24 islands / 1f of the island component, after forming a fiber layer (A) with the sea-island type composite short fiber, a three-dimensional interwoven body of the fiber and loose coarse cloth is formed by a needle punching treatment, etc., and after filling the three-dimensional interwoven body with PU resin, the sea component is dissolved or decomposed, thereby obtaining an ultrafine fiber with a single fiber fineness equivalent to 0.2 dtex. At this time, the fiber bundle of 24 single fibers exists in the fiber layer (A) in a state of being bundled (corresponding to 4.8 dtex in the bundled state).
[0123] When the fiber layer (A) is composed of fibers dispersed in a single fiber, the surface smoothness is excellent. For example, when the outer surface of the fiber layer (A) is raised by polishing, uniform raising is easily obtained, and even when the adhesion rate of the PU resin is low, it is difficult to produce a pilling-like appearance called pilling due to friction, so that artificial leather with better surface quality and wear resistance can be obtained. In addition, when the fibers are dispersed in a single fiber, the fiber spacing is likely to become narrow and uniform, so even if the PU resin is attached in a fine form, good wear resistance can be obtained. As methods for dispersing the fibers into single fibers, there can be listed: a method of sheeting fibers produced by a direct spinning method using a papermaking method; a method of dissolving or decomposing the sea component of a fiber sheet made of sea-island type composite fibers to produce ultrafine fiber bundles, and then subjecting the ultrafine fiber bundle surface to the aforementioned water flow dispersion treatment to promote the single fiberization of the ultrafine fiber bundles, etc.
[0124] In the fiber layers other than the fiber layer (A) among the fiber layers constituting the artificial leather, the fibers may be dispersed in the form of single fibers or not. In a preferred embodiment, the layers other than the fiber layer (A) are composed of fibers dispersed in the form of single fibers. It is preferred that the fibers constituting the layers other than the fiber layer (A) are dispersed in the form of single fibers, from the viewpoint of making the thickness of the artificial leather uniform, improving the processing accuracy, and stabilizing the quality, and also from the viewpoint of making the appearance of the front and back of the artificial leather homogeneous.
[0125] When the artificial leather is composed only of the fiber layer (A), the weight per unit area of the fibers constituting the fiber layer (A) is preferably 40 g / m2 from the viewpoint of mechanical strength such as abrasion resistance. 2 Above and 500g / m 2 Below, more preferably 50g / m 2 Above and 370g / m 2 Below, more preferably 60g / m 2 Above and 320g / m 2 the following.
[0126] When the artificial leather is composed of a three-layer structure of a fiber layer (A), loose cloth and a fiber layer (B), the weight per unit area of the fibers constituting the fiber layer (A) is preferably 10 g / m2 from the viewpoint of mechanical strength such as abrasion resistance. 2 Above and 200g / m 2 Below, more preferably 30g / m 2 Above and 170g / m 2 Below, more preferably 60g / m 2 Above and 170g / m 2 In addition, from the viewpoint of cost and ease of production, the weight per unit area of the fibers constituting the fiber layer (B) is preferably 10 g / m2 Above and 200g / m 2 Below, more preferably 20g / m 2 Above and 170g / m 2 From the viewpoint of mechanical strength and the interweaving property between the fiber layer and the loose cloth, the weight per unit area of the loose cloth is preferably 20 g / m 2 Above and 150g / m 2 Below, more preferably 20g / m 2 Above and 130g / m 2 Below, more preferably 30g / m 2 Above and 110g / m 2 the following.
[0127] The weight per unit area of the artificial leather filled with PU resin is preferably 50 g / m 2 Above and 550g / m 2 Below, more preferably 60g / m 2 Above and 400g / m 2 Below, more preferably 70g / m 2 Above and 350g / m 2 the following.
[0128] In one embodiment, the texture (softness and hardness value) of the artificial leather is preferably 28 cm or less, more preferably 6 cm or more and 26 cm or less, and further preferably 8 cm or more and 22 cm or less. The softness and hardness value is an index indicating the texture of the artificial leather. By setting the softness and hardness value to 28 cm or less, the formability of the surface material or interior material of the sheet of interior decoration, automobile, airplane, train, etc. is improved, and the consumption performance is also improved, and the softness is easy to meet the needs sought in the market.
[0129] In one embodiment, the density (dispersion of fiber bundles) of the artificial leather is preferably 4.0 or higher, more preferably 5.0 or higher. The density (dispersion of fiber bundles) refers to a value in which the density of the fuzz is judged into 7 levels by visual and tactile sensory evaluation. By setting the density to 4.0 or higher, the quality of the surface material or interior material of the sheet for interior decoration, automobiles, airplanes, trains, etc. is improved.
[0130] <Method for producing artificial leather>
[0131] Hereinafter, an example of the method for producing the artificial leather according to the present embodiment will be described.
[0132] An example of the method for producing artificial leather according to the present embodiment may include the following steps:
[0133] A step of forming a fiber web with sea-island staple fibers, and then subjecting the fiber sheet obtained by needle punching to sea-removal treatment to obtain a fiber sheet in which single fibers of island components are exposed; and
[0134] The step of subjecting the obtained fiber sheet to a water jet dispersion treatment to obtain a fiber sheet in which single fibers are dispersed,
[0135] The following steps may be further included:
[0136] The process of impregnating the fiber sheet in which the single fibers are dispersed with a water-dispersible PU resin dispersion containing hot water-soluble resin particles, and then heating the PU resin to adhere the PU resin to obtain a sheet-like object filled with the PU resin; and
[0137] A step of removing the hot water-soluble resin fine particles from the obtained sheet-like product using hot water.
[0138] Hereinafter, each step will be described in order.
[0139] [Step of forming a fiber web using sea-island staple fibers, and then subjecting the fiber sheet obtained by needle punching to sea-removal treatment to obtain a fiber sheet in which single fibers of the island component are exposed]
[0140] As a method for producing each fiber layer (fiber layer (A), optional fiber layer (B), etc.) constituting the fiber sheet of artificial leather, there can be cited a spinning direct bonding method (e.g., spunbond method and meltblown method) or a method for forming a fiber sheet using short fibers (e.g., dry methods such as carding method and air-laid method; and wet methods such as papermaking method), all of which can be appropriately used. In this embodiment, sea-island (SIF) short fibers are used as a raw material. The fiber sheet produced using short fibers has a small variation in weight per unit area, excellent uniformity, and is easy to obtain uniform fuzzing, and is therefore suitable from the viewpoint of improving the surface quality of artificial leather.
[0141] The means for forming the ultrafine fibers of the fiber sheet can use ultrafine fiber-expressing fibers. By using ultrafine fiber-expressing fibers, a form in which ultrafine fiber bundles are entangled can be stably obtained.
[0142] As ultrafine fiber-expressing fibers, there can be used: sea-island type fibers in which two thermoplastic resins with different solvent solubility are used as sea components and island components, and the sea components are dissolved and removed using a solvent or the like to make the island components into ultrafine fibers; and strippable composite fibers in which two thermoplastic resins are alternately arranged in a radial or multi-layered manner on the fiber cross section, and each component is stripped and split to form ultrafine fibers. Among them, the sea-island type fibers can provide appropriate gaps between the island components, that is, between the ultrafine fibers, by removing the sea component, and therefore are preferably used from the viewpoint of the softness and texture of the sheet.
[0143] The sea-island type fiber includes: a sea-island type composite fiber in which the sea component and the island component are arranged and spun using a sea-island type composite head; a sea-island type mixed fiber in which the sea component and the island component are mixed and spun, etc. From the viewpoint of obtaining ultrafine fibers of uniform fineness and obtaining ultrafine fibers of sufficient length to contribute to the strength of the sheet, it is preferred to use the sea-island type composite fiber.
[0144] As the sea component of the sea-island type fiber, polyethylene, polypropylene, polystyrene, copolymerized polyesters copolymerized with sodium sulfoisophthalic acid, polyethylene glycol, etc., and polylactic acid, etc. Among them, alkali-decomposable copolymerized polyesters copolymerized with sodium sulfoisophthalic acid, polyethylene glycol, etc., which can be decomposed without using an organic solvent, and polylactic acid are preferred from the viewpoint of environmental protection.
[0145] When using sea-island type fibers, the sea-removal treatment is preferably performed before applying PU resin to the fiber sheet. If the sea-removal treatment is performed before applying PU resin, the PU resin directly adheres to the ultrafine fibers, and the ultrafine fibers can be firmly held, so the wear resistance of the sheet becomes good.
[0146] As a method for interweaving the fibers or fiber bundles of a fiber web, the following methods can be used: cutting the sea-island type fibers into a specified fiber length to form a hair bundle, forming a fiber web by combing and cross-laying, and interweaving them by a water flow interweaving treatment called needle punching or water flow interweaving.
[0147] In the needle punching method, the number of barbs of the needle used is preferably 1 to 9. By setting the number of barbs to 1 or more, an interlacing effect can be obtained and fiber damage can be suppressed. By setting the number of barbs to 9 or less, fiber damage can be reduced and needle marks remaining on the artificial leather can be reduced, thereby improving the appearance of the product.
[0148] Considering the interweaving of the fibers and the effect on the appearance of the product, the total depth of the barbs (the length from the front end of the barbs to the bottom of the barbs) is preferably 0.05 mm or more and 0.10 mm or less. By making the total depth of the barbs 0.05 mm or more, it is possible to obtain good hooking of the fibers, and thus, efficient fiber interweaving can be performed. In addition, by making the total depth of the barbs 0.10 mm or less, the needle marks remaining in the artificial leather are reduced, and the quality is improved. Considering the balance between the strength of the barb portion and the interweaving of the fibers, the total depth of the barbs is more preferably 0.06 mm or more and 0.08 mm or less.
[0149] When the fibers are entangled by needle punching, the needle punching density is preferably set to 300 needles / cm 2 Above 6000 / cm 2Below, more preferably 1000 strands / cm 2 Above 6000 / cm 2 the following.
[0150] The fiber sheet obtained by the needle punching treatment can be made into a fiber sheet before sea removal by, for example, immersing it in water at a temperature of 98° C. for 2 minutes to shrink it, and drying it at a temperature of 100° C. for 5 minutes.
[0151] The sea-removal treatment can be carried out by immersing the sea-island type fiber in a solvent and squeezing out the liquid. As a solvent for dissolving the sea component, when the sea component is copolyester or polylactic acid, an alkaline aqueous solution such as sodium hydroxide can be used. From the perspective of environmental protection of the process, the sea-removal treatment using an alkaline aqueous solution such as sodium hydroxide is preferred.
[0152] Regarding the length of the short fibers when the method of using the short fibers (tresses) is selected, in the dry method (carding method, air-laid method, etc.), it is preferably 13 mm or more and 102 mm or less, more preferably 25 mm or more and 76 mm or less, and further preferably 38 mm or more and 76 mm or less. In the wet method (papermaking method, etc.), it is preferably 1 mm or more and 30 mm or less, more preferably 2 mm or more and 25 mm or less, and further preferably 3 mm or more and 20 mm or less. For example, the ratio of the length (L) to the diameter (D) of the short fibers used in the wet method (papermaking method, etc.), that is, the aspect ratio (L / D) is preferably 500 or more and 2000 or less, and more preferably 700 to 1500. Regarding this aspect ratio, when the short fibers are dispersed in water to prepare the slurry, the dispersibility and fiber opening of the short fibers in the slurry are good, the fiber layer strength is good, the fiber length is short and the single fibers are easily dispersed compared to the dry method, so it is not easy to present a fluffy appearance called pilling due to friction, so it is preferred. For example, the fiber length of short fibers having a diameter of 4 μm is preferably from 2 mm to 8 mm, and more preferably from 3 mm to 6 mm.
[0153] [Step of subjecting the obtained fiber sheet to water jet dispersion treatment to obtain a fiber sheet in which single fibers are dispersed]
[0154] By subjecting the obtained fiber sheet to the aforementioned water flow dispersion treatment, a fiber sheet in which single fibers are dispersed can be obtained. By subjecting the obtained fiber sheet to the aforementioned water flow dispersion treatment after the sea removal step, the k-neighbor distance ratio value (k=9, radius r=20 μm) between the single fiber cross sections constituting the fiber layer (A) in the thickness direction cross section of the artificial leather can be controlled to be less than 80%.
[0155] [Step of impregnating the fiber sheet in which the single fibers are dispersed with a water-dispersible PU resin dispersion containing hot water-soluble resin particles, and then heating the PU resin to adhere the PU resin to obtain a sheet-like object filled with the PU resin]
[0156] In this process, the fiber sheet is impregnated with a water-dispersed PU resin dispersion containing hot water-soluble resin particles, and then the PU resin is adhered by heating to fill the fiber sheet with the PU resin. In a typical method, the PU resin is impregnated in the form of an impregnation liquid such as a dispersion (for example, in the case of a water-dispersed type). The concentration of the PU resin in the impregnation liquid can be, for example, 10 to 35% by mass. In one method, the impregnation liquid is prepared and impregnated into the fiber sheet in such a manner that the ratio of the PU resin to 100% by mass of the fiber sheet is 15 to 50% by mass.
[0157] Water-dispersible PU resins are classified into: forced emulsified PU resins that are forcibly dispersed / stabilized using a surfactant; and self-emulsified PU resins that have a hydrophilic structure in the PU molecular structure and are dispersed / stabilized in water even without a surfactant. In this embodiment, any of them can be used, but from the perspective of imparting the thermosensitive coagulation property described later, it is preferred to use a forced emulsified PU resin.
[0158] In the present embodiment, the fiber sheet is impregnated with a water-dispersible PU resin dispersion containing hot water-soluble resin particles, but it is not preferred to dissolve the hot water-soluble resin particles in the water-dispersible PU resin dispersion. On the other hand, the hot water-soluble resin particles show the property of being more difficult to dissolve in an aqueous solution containing a surfactant than water, and therefore, a forced emulsification PU resin dispersion containing a surfactant is a more preferred method than a self-emulsification PU resin dispersion containing no surfactant. From the viewpoint of controlling the amount of adhesion of the water-dispersible PU resin, and from the viewpoint that if the concentration is high, the aggregation of the PU resin is promoted and the stability of the aforementioned impregnation liquid is reduced, the concentration of the water-dispersible PU resin (the content of the PU resin relative to the water-dispersible PU resin dispersion) is preferably 10 to 35% by mass, more preferably 15 to 30% by mass, and further preferably 15 to 25% by mass.
[0159] In addition, as a water-dispersible PU resin dispersion, it is preferred to have thermosensitive coagulation. By using a water-dispersible PU resin dispersion having thermosensitive coagulation, PU resin can be uniformly imparted in the thickness direction of the fiber sheet. Thermosensitive coagulation refers to the property that when the PU resin dispersion is heated, if a certain temperature (thermosensitive coagulation temperature) is reached, the fluidity of the PU resin dispersion is reduced and coagulated. In the manufacture of a sheet filled with PU resin, after the PU resin dispersion is infiltrated into the fiber sheet, it is coagulated by dry heat coagulation, wet heat coagulation, hot water coagulation or a combination thereof, and dried, thereby imparting PU resin to the fiber sheet. As a method for coagulating a water-dispersible PU resin dispersion that does not show thermosensitive coagulation, dry coagulation is realistic in industrial production, but at this time there is a tendency that the PU resin migrates to the surface of the sheet, and the texture of the sheet filled with PU resin solidifies.
[0160] The thermosensitive coagulation temperature of the aqueous PU resin dispersion is preferably 40 to 90° C. By setting the thermosensitive coagulation temperature to 40° C. or higher, the stability of the PU resin dispersion during storage becomes good, and the adhesion of the PU resin to the machine during actual operation can be suppressed. In addition, by setting the thermosensitive coagulation temperature to 90° C. or lower, the migration of the PU resin in the fiber sheet can be suppressed.
[0161] In order to make the thermosensitive coagulation temperature as described above, a thermosensitive coagulant may be appropriately added. Examples of the thermosensitive coagulant include inorganic salts such as sodium sulfate, magnesium sulfate, calcium sulfate, and calcium chloride; and free radical reaction initiators such as sodium persulfate, potassium persulfate, ammonium persulfate, azobisisobutyronitrile, and benzoyl peroxide.
[0162] The water-dispersible PU resin dispersion can be impregnated and applied to a fiber sheet, etc., and the PU resin can be coagulated by dry heat coagulation, wet heat coagulation, hot water coagulation or a combination thereof. The temperature of wet heat coagulation is set to be above the thermosensitive coagulation temperature of the PU resin, preferably 40 to 200°C. By setting the temperature of wet heat coagulation to be above 40°C, more preferably to be above 80°C, the time until the PU resin is coagulated can be shortened, and the migration phenomenon can be further suppressed. On the other hand, by setting the temperature of wet heat coagulation to be below 200°C, more preferably to be below 160°C, thermal degradation of the PU resin and PVA resin can be prevented. The temperature of hot water coagulation is set to be above the thermosensitive coagulation temperature of the PU resin, preferably to 40 to 100°C. By setting the hot water coagulation temperature in hot water to be above 40°C, more preferably to be above 80°C, the time until the PU resin is coagulated can be shortened, and the migration phenomenon can be further suppressed. The dry coagulation temperature and the drying temperature are preferably 80 to 180°C. The productivity is excellent by setting the dry coagulation temperature and the drying temperature to 80°C or higher, more preferably 90°C or higher. On the other hand, the thermal degradation of the PU resin and the PVA resin can be prevented by setting the dry coagulation temperature and the drying temperature to 180°C or lower, more preferably 160°C or lower.
[0163] As described above, when the fiber sheet in which the single fibers are dispersed is impregnated with a water-dispersible PU resin dispersion containing hot water-soluble resin particles, the content of the hot water-soluble resin particles in the water-dispersible PU resin dispersion is preferably 1% by weight or more and 20% by weight or less, more preferably 2% by weight or more and 15% by weight or less, and even more preferably 3% by weight or more and 10% by weight or less. By including hot water-soluble resin particles in the water-dispersible PU resin dispersion, further dispersion of the PU resin mass is promoted.
[0164] [Step of removing the hot water-soluble resin fine particles from the obtained sheet-like product using hot water]
[0165] As means for removing hot water-soluble resin from a sheet, the following methods can be cited, for example: a method of immersing it in hot water above 60°C, preferably above 80°C; a method of removing hot water-soluble resin particles while circulating hot water above 80°C before dyeing in a liquid flow dyeing machine, etc. In particular, the method of removing hot water-soluble resin particles in a liquid flow dyeing machine can omit the steps of drying and winding the sheet after removing the hot water-soluble resin particles, which can improve production efficiency and is preferred in this regard. In the present embodiment, a soft sheet is obtained by removing hot water-soluble resin particles from the sheet after imparting PU resin. The method for removing hot water-soluble resin particles is not particularly limited. For example, it is preferred to immerse the sheet in hot water at 60 to 100°C and to dissolve and remove the particles by squeezing the liquid with a cloth mill or the like as needed.
[0166] [Post-process]
[0167] After the fiber sheet is filled with PU resin and the hot water soluble resin particles are removed, the sheet filled with PU resin can be cut in half along the thickness direction of the sheet without loose cloth. This can improve production efficiency.
[0168] In addition, before the fluffing treatment described below, a lubricant such as a silicone dispersion may be applied to the sheet filled with the PU resin. In addition, applying an antistatic agent before the fluffing treatment is a preferred method for preventing grinding powder generated by the sheet from being easily deposited on the sandpaper.
[0169] In order to form standing hairs on the surface of the sheet, a raising treatment may be performed. The raising treatment can be performed by grinding with sandpaper, a roller polisher, or the like. In addition, when silicone or the like is applied as a lubricant before the raising treatment, the hairs can be easily raised by surface grinding, and the surface quality is very good.
[0170] Artificial leather is preferably dyed for the purpose of improving the value of sensibility (i.e., visual effect). The dye can be selected according to the type of fiber constituting the fiber sheet. For example, if it is a polyester fiber, a disperse dye can be used, and if it is a polyamide fiber, an acid dye or a gold-containing dye can be used, and further, a combination thereof can be used. When dyeing with a disperse dye, reduction cleaning can be performed after dyeing. As a dyeing method, a common method known to dyeing processing industry can be used. As a dyeing method, a liquid flow dyeing machine is preferably used from the aspect of being able to give a rubbing effect while dyeing the sheet to soften the sheet. The dyeing temperature also varies depending on the type of fiber, preferably 80 to 150°C. By setting the dyeing temperature to above 80°C, more preferably to above 110°C, the fiber can be dyed with good efficiency. On the other hand, by setting the dyeing temperature to below 150°C, more preferably to below 130°C, the deterioration of the PU resin can be prevented.
[0171] Preferably, the artificial leather dyed in this way is subjected to soaping and reduction cleaning (i.e., cleaning in the presence of a chemical reducing agent) as required to remove unnecessary dye. In addition, it is also a preferred mode to use a dyeing auxiliary when dyeing. By using a dyeing auxiliary, it is possible to improve the uniformity and reproducibility of dyeing. In addition, softeners such as silicone, antistatic agents, water repellents, flame retardants, lightfast agents, antibacterial agents, etc. can be used to implement finishing agent processing while dyeing or after dyeing.
[0172] The artificial leather of this embodiment can be suitably used as surface materials for furniture, chairs, wall materials, seats, ceilings, interior decorations, etc. in cars, trains, airplanes, etc.; interior materials with very beautiful appearance, uppers, trims, etc. of shoes such as shirts, jackets, casual shoes, sports shoes, men's shoes, women's shoes, bags, belts, wallets, etc., clothing materials used as parts of them, wiping cloths, polishing cloths, CD curtains, and other industrial materials.
[0173] Example
[0174] The present invention will be described in detail below based on Examples and Comparative Examples, but the Examples do not limit the scope of the present invention. The artificial leather samples described in the Examples and Comparative Examples were evaluated for various physical properties, quality, etc. by the following procedures and methods.
[0175] (1) Sample collection site
[0176] Figure 3 The locations where samples were collected are shown.
[0177] First, 10 approximately equal parts (sampling areas 1, 2, ...) in the machine direction (MD) of the fiber layer (A) or the artificial leather containing the fiber layer (A) are cut into strips (indicated by dotted lines). A section in the thickness (t) direction is made in each sampling area. Conductive treatment is performed by coating and processing 1nm of osmium atoms on the produced section in the thickness (t) direction. In order to obtain the single fiber cross-section k neighbor distance ratio (%) and the cross-section PU resin area ratio (%) in the cross section, SEM images of 10 approximately equal parts in the CD direction orthogonal to the MD direction are taken. In addition, in order to obtain the surface PU resin area ratio (%) in each sampling area, the first outer surface of the fiber layer (A) is coated and processed with 1nm of osmium atoms at 10 approximately equal parts in the CD direction for conductive treatment, and an SEM image of its first outer surface is taken. In addition, in order to obtain the spatial dimensions in each sampling area, three-dimensional images based on X-ray CT are taken at 10 approximately equal parts in the CD direction. That is, 100 images are prepared for each of the images used to obtain the single fiber cross-section k-neighbor distance ratio (%), cross-section PU resin area ratio (%), and spatial size. In this case, the average value and standard deviation of each value are set to the amount of 100 images.
[0178] In addition, when the artificial leather is napped, the napping direction can be determined to be the MD direction. When the artificial leather is not napped and the MD direction is unknown, the sample may be cut out in any one direction and in a direction orthogonal thereto.
[0179] (2) Ratio of k-neighbor distance of single fiber cross section (%)
[0180] like Figure 5As shown, the k-nearest neighbor method is a method of taking k single fiber cross sections close to any single fiber cross section and using the radius closest to the kth one in Euclidean distance as a method of determining a boundary.
[0181] In this embodiment, in one SEM image, a range of about 250 μm × about 186 μm (in this case, 1 pixel is equivalent to about 0.40 μm × about 0.40 μm) is photographed under the conditions of a band under the image and 640 × 480 pixels, and it is determined whether there is a single fiber section close to k = 9 within a distance of 20 μm from the approximate center of any single fiber section. For all single fiber sections in one SEM image, the existence is determined, and the ratio value (%) of the k = 9 neighbor distance of the single fiber section is calculated using the following formula:
[0182] The neighbor distance ratio value (%) of a single fiber cross section (k=9) = {(the number of single fiber cross sections close to the k=9th single fiber cross section within a distance of 20 μm from the approximate center of the single fiber cross section) / (the total number of single fiber cross sections in one SEM image)}×100.
[0183] In addition, the ratio value (%) of the neighbor distance of the single fiber cross section k=9 is the average value of each value calculated from 100 SEM images. In addition, when the sample has a loose cloth, the deepest part of the fiber layer (A) in the above-mentioned cut surface of the sample treated with conductivity (i.e., the part closest to the loose cloth side) is used as the observation area, and the fibers constituting the loose cloth are excluded from the observation object, and observation is performed using a scanning electron microscope (SEM, "JSM-5610" manufactured by JEOL Ltd.). When the sample does not have a loose cloth, the central part of the artificial leather thickness direction in the above-mentioned cut surface of the sample treated with conductivity is used as the center point of the observation area, and observation is performed using the aforementioned SEM.
[0184] The single fiber cross section in the SEM image is shown in Figure 4 As shown, by marking by a person, its existence can be identified. The specific steps are as follows:
[0185] [Step 1]
[0186] In the SEM image (gray), the fiber cross section is marked with a red (R) dot, and the coordinates of the fiber cross section are calculated.
[0187] <Detailed method>
[0188] (i) Use OpenCV (cv2 module for Python) to read the image.
[0189] (ii) Extract pixels whose R of RGB is greater than or equal to 220 and whose G and B are less than or equal to 100.
[0190] (iii) For noise processing, the detected dots are subjected to dilation processing (processing with iteration=2 for cv2.dilate) and contraction processing (processing with iteration=2 for cv2.erode).
[0191] (iv) The noise-processed image is processed using cv2.connected Component With Stats to obtain the centroid coordinates of the circle point detected as the third result among the four results obtained.
[0192] (v) The above centroid coordinates are used as the fiber cross-sectional position.
[0193] (vi) Furthermore, the distance between specific positions on the coordinates is calculated. When the coordinates of the fiber cross section A and the fiber cross section B are (Ax, Ay) and (Bx, By), the two Euclidean distances R are calculated using R = √((Ax-Bx) 2 +(Ay-By) 2 ) to calculate.
[0194] [Step 2]
[0195] For all fiber cross sections, the Euclidean distance to the k-th fiber cross section (k nearest neighbor distance: row-column distance) is calculated.
[0196] <Detailed method>
[0197] (i) Calculate the distance between the coordinates of fiber section A and other sections.
[0198] (ii) Arrange the calculated distances in ascending order.
[0199] (iii) The kth distance of the arrangement is taken as the k nearest neighbor distance.
[0200] [Step 3]
[0201] The k-neighbor distance ratio value in the SEM image was obtained by dividing the number of cross sections with a k-neighbor distance of R or less by the number of all fiber cross sections.
[0202] In addition, when there are multiple SEM images, machine learning (deep learning) can be used to replace human marking and determine the position of the fiber cross section. In the machine learning, images of teacher data (correct labels) containing red (R) dots marked in the fiber cross section are used as learning data, and semantic segmentation using a network FCN (Fully Convolutional Networks) method composed entirely of folded layers (Jonathan Long, Evan Shelhamer, and Trevor Darrel (2015): Fully Convolutional Networks for Semantic Segmentation. In The IEEE Conference on Computer Vision and Pattern Recognition (CVPR)) is used to perform level classification at the pixel level.
[0203] (3) Cross-sectional PU resin area ratio (%) and standard deviation
[0204] Pre-treatment
[0205] After cutting the sample in the thickness direction section into 1cm×0.5cm (horizontal (x)×vertical (y)), the internal space of the sample is embedded with an epoxy resin (main agent: "Quetol812" manufactured by Nissin EM, curing agent: "MNA" manufactured by Nissin EM, accelerator: "DMP-30" manufactured by Nissin EM). The obtained resin-embedded sample is cut parallel to the thickness direction using a microtome to obtain a smooth cut surface. Next, it is allowed to stand in the saturated vapor of ruthenium tetroxide for 4 hours, and the PU resin attached to the sample is electronically stained with ruthenium. Next, a conductive treatment is performed by coating and processing 1nm of osmium atoms.
[0206] ·observe
[0207] When the sample has a loose cloth, the deepest part of the fiber layer (A) in the above-mentioned cut surface of the conductively treated sample (i.e., the part closest to the loose cloth side) is used as the observation area, and the fibers constituting the loose cloth are excluded from the observation object, and observation is performed using a scanning electron microscope (SEM, "SU8220" manufactured by Hitachi High-Technologies Corporation). In addition, when the sample does not have a loose cloth, the central part of the artificial leather thickness direction in the above-mentioned cut surface of the conductively treated sample is used as the center point of the observation area, and observation is performed using the aforementioned SEM. The observation conditions are as follows.
[0208] Accelerating voltage: 10 kV
[0209] Detector: YAG-BSE (ring-shaped scintillator type reflected electron)
[0210] Camera magnification: 500 times
[0211] Observation field: about 230μm×about 173μm
[0212] Image analysis
[0213] The obtained SEM reflection electron image was binarized using the image analysis software "ImageJ (version number: 1.51j8, National Institutes of Health, USA) by the following method to determine the average size of the PU resin.
[0214] (i) Filter processing is performed on the SEM image. The processing conditions are as follows:
[0215] Bandpass filter processing Filter large structures down to 40pixels, Filter smallstructures up to 3pixels, Suppress stipes None, Tolerance of direction 5%, Autoscale after filtering, Saturate image when autoscaling, on this basis, it is processed as a median filter, radius: 4, 1-order filter processing.
[0216] (ii) Binarization was performed using the MaxEntropy method, and the black portion in the binarized SEM image was regarded as the PU resin.
[0217] (iii) The area ratio of the PU resin to each partition is calculated from the obtained binary image.
[0218] like Figure 6 As shown, the obtained binary image (1280×960 pixels, 1280×896 pixels if the band under the image is removed) is partitioned into 32×32 pixels (1120 partitions at this time), and the total area of each PU resin distributed in each partition is divided by the area of each partition using the AnalyzeParticle function of ImageJ (conditions: Size = 0-infinity, Circularity = 0.00-1.00) to obtain the value obtained as the cross-sectional PU resin area ratio (%) of each partition. Read the number of pixels on the x and y axes of the target image, specify the partition size with the pixel size, find the number of divisions on the x and y axes, and calculate the PU resin area % in each partitioned area.
[0219] The area ratio of the PU resin calculated from one SEM image is the ratio obtained by averaging the area ratios of the PU resin in all the sections of one SEM image, and its standard deviation is given by Figure 6 Calculate using the formula shown.
[0220] In addition, the cross-sectional PU resin area ratio (%) and standard deviation are the average values of the area ratio and standard deviation of the PU resin calculated from one SEM image and 100 images. Figure 6 As shown, first, for one SEM image, the standard deviation is calculated for all the partitions divided into partitions, and the average of the standard deviations calculated for 100 SEM images is taken as the standard deviation.
[0221] (4) Average diameter of single fibers constituting the fiber layer (A) (μm)
[0222] The average diameter of the fibers constituting the fiber layer (A) is calculated as follows: For the cross-section in the thickness direction of the fiber layer (A) constituting the artificial leather, 10 SEM images are taken at a magnification of 1500 times using a scanning electron microscope (SEM, "JSM-5610" manufactured by JEOL Ltd.), 100 fibers forming the first outer surface of the artificial leather are randomly selected, and the diameter of the cross-section of the single fiber is measured, which is taken as the arithmetic mean of the 100 measured values.
[0223] When the observed shape of the cross section of a single fiber is not circular, the distance between the outer circumferences on a straight line perpendicular to the midpoint of the longest diameter of the cross section of the single fiber is taken as the fiber diameter.
[0224] Figure 2 is a conceptual diagram illustrating the method of calculating the fiber diameter. Figure 2 In this way, when the cross section A of the fiber is elliptical, the distance c between the outer circumferences on the straight line b orthogonal to the midpoint p of the longest diameter a of the cross section A in the observation image is taken as the fiber diameter.
[0225] (5) Spatial size (μm)
[0226] A three-dimensional image of the fiber layer (A) is taken using X-ray CT, and the average value in the thickness direction of the diameter (μm) of the largest sphere that enters the space after the fibers and PU resin blocks that constitute the fiber layer (A) are removed is used as the spatial dimension and is calculated using the following steps.
[0227] (i) The image is rotated on the screen so that the xz axis is in the plane and the y axis is in the thickness direction, and the image is trimmed into a rectangular parallelepiped.
[0228] (ii) Median filtering is performed with a radius of 2pix.
[0229] (iii) The Otsu method is applied to segment the regions. The brightness value of the pixels is set to 0 for air and 255 for nonwoven fabric fibers and urethane resin.
[0230] (iv) For pixels with a brightness value of 255 (fiber, PU resin), segmentation using an image processing method is performed, and structures where the number of pixels (pix) of a continuous portion with a brightness value of 255 is 10,000 or less are removed as noise.
[0231] (v) For a brightness value of 0 (air), the thickness method of image analysis is performed to obtain the spatial size. All pixels of a three-dimensional image have a value of the spatial size.
[0232] (vi) The two-dimensional original image of the xz plane is cut out along the y axis (thickness direction) with a thickness of 1 pix, and the average and standard deviation of the spatial dimensions in the plane are calculated.
[0233] (vii) The above step (vi) is performed for all y to obtain the profile in the thickness direction.
[0234] In addition, the spatial size (μm) and the standard deviation are the average values of the respective values calculated from 100 three-dimensional images based on X-ray CT. In addition, when the sample has a loose cloth, the deepest part of the fiber layer (A) (i.e., the part closest to the loose cloth side) is used as the observation area, and the fibers constituting the loose cloth are excluded from the observation object, and the image is taken using an X-ray CT device ("High Resolution 3D X-ray Microscope" manufactured by Rigaku Co., Ltd.). In addition, when the sample does not have a loose cloth, the central part of the thickness in the cross section in the thickness direction is used as the center point of the observation area and the image is taken.
[0235] (6) Calculation of texture (softness and hardness value)
[0236] Cut each sample into a 20cm×20cm square as a measurement sample. Place the measurement sample on a horizontal plane, set the vertices of the square to A, B, C, and D, and make the vertices A and C opposite to each other on the diagonal line overlap. Place vertex A on a horizontal plane, and make vertex C overlap with vertex A. Next, slowly move vertex C away from vertex A along the diagonal AC while in contact with the measurement sample, set the point where vertex C leaves the measurement sample surface to point E, and set the distance between point E and vertex C to softness value 1. Replace vertex A with vertex B and vertex C with vertex D, and measure softness value 2 using the same steps as above. The arithmetic mean of softness value 1 and softness value 2 is taken as the texture (softness and hardness value) of the sample. In addition, when the artificial leather is a single layer, the average value of 10 samples is taken as the texture (softness and hardness value). When the artificial leather has a two-layer structure or a three-layer structure, the average value of 5 samples measured with the fiber layer (A) constituting the artificial leather on the upper side and 5 samples measured with the fiber layer (A) on the lower side is taken as the texture (softness and hardness value).
[0237] (7) Density (dispersion of fiber bundles)
[0238] The samples were evaluated by 20 evaluators, 10 male and 10 female adults in good health, and visually and sensoryly evaluated in 7 stages according to the following criteria, with the highest evaluation being set as the denseness. Regarding the denseness (dispersion of the fiber bundles), 4.0 to 7.0 was considered good (passed).
[0239] Level 7: The nap is very dense and the appearance is very good.
[0240] Level 6: Evaluation between Level 7 and Level 5.
[0241] Level 5: The nap is dense and the appearance is good.
[0242] Level 4: Evaluation between Level 5 and Level 3.
[0243] Grade 3: The entire surface is evenly fuzzy and has a leather-like appearance.
[0244] Level 2: Evaluation between Level 3 and Level 1.
[0245] Level 1: Sparse fuzz and poor appearance.
[0246] In addition, the average value of 10 samples was used as the level of denseness.
[0247] (8) Adhesion rate of PU resin to fiber sheet
[0248] The adhesion rate of the PU resin to the fiber sheet was measured by the following method.
[0249] The mass of the fiber sheet before impregnation with the PU resin is defined as A (g). The fiber sheet is impregnated with the PU resin dispersion, then heated and dried at 130°C using a pin tenter dryer, then kneaded while immersed in hot water heated to 90°C, and then dried to obtain a fiber sheet filled with PU resin (hereinafter also referred to as a "resin-filled fiber sheet"). The mass of the resin-filled fiber sheet is defined as B (g). The adhesion rate (C) of the PU resin is calculated using the following formula.
[0250] C=(BA) / A×100(wt%)
[0251] (9) Average primary particle size of PU resin in PU resin dispersion
[0252] The particle size distribution was measured using a laser diffraction particle size analyzer ("LA-920" manufactured by Horiba, Ltd.) in accordance with the measurement manual of the analyzer, and the median particle size was defined as the average primary particle size.
[0253] (10) Saponification degree of PVA resin particles contained in PU resin dispersion
[0254] The measurement was conducted in accordance with JIS K 6726 (1994) 3.5.
[0255] (11) Degree of polymerization of PVA resin particles contained in PU resin dispersion
[0256] The measurement was conducted in accordance with JIS K 6726 (1994) 3.7.
[0257] (12) Average particle size (μm) of PVA resin microparticles contained in PU resin dispersion
[0258] As fine particles, "NL-05" manufactured by Mitsubishi Chemical Corporation can be used. The hot water-soluble resin fine particles are fined in accordance with the method described in Japanese Patent Application Laid-Open No. 7-82384.
[0259] (13) Turbulence of water jetted from nozzles during water jet dispersion treatment
[0260] The turbulence of the water flow ejected from the nozzle in the water flow dispersion treatment was measured by the following method.
[0261] The water flow ejected from the nozzle was photographed using a single-lens camera (Nikon's "D600") equipped with a telecentric lens (Sill Optics GmbH & Co. KG's "S5LPJ007 / 212") to obtain image data. The image data was read into a PC, and the water flow within a range of 25 mm to 35 mm from the nozzle hole was cut to measure the water flow diameter for each pixel column (about 6 μm) in the width direction of the water flow. Based on all the measured data, the average diameter W and standard deviation σ of the water flow within a range of 25 mm to 35 mm from the nozzle hole were calculated, and the turbulence was calculated using the following formula.
[0262] Turbulence (%)=σ(mm) / W(mm)×100
[0263] It should be noted that the turbulence is assumed to be an average value of values obtained from five pieces of image data.
[0264] [Example 1]
[0265] As the sea component, polyethylene terephthalate copolymerized with 8 mol% of 5-sodium sulfonate is used, and as the island component, polyethylene terephthalate is used, with a composite ratio of 20% by mass of the sea component and 80% by mass of the island component, to obtain a sea island type composite fiber with an island number of 16 islands / 1f and an average fiber diameter of 18 μm. The obtained sea island type composite fiber was cut into a fiber length of 51 mm to form a tuft, and a fiber web was formed by combing and cross-laying, and a fiber sheet was obtained by needle punching. The obtained fiber sheet was immersed in 95°C hot water to shrink it, and dried at 100°C for 5 minutes using the pin tenter dryer to obtain a fiber sheet with a unit area weight of 600 g / m 2 A single layer of fiber sheets.
[0266] The obtained fiber sheet was immersed in a sodium hydroxide aqueous solution heated to 95°C and having a concentration of 10 g / L for 25 minutes to remove the sea component of the sea-island composite fiber. The average diameter of single fibers constituting the fiber sheet after sea removal was 4 μm.
[0267] Next, a three-row straight-flow jet nozzle with a nozzle hole spacing of 0.25 mm, a turbulence of 17%, an aperture of 0.10 mm was used to spray high-speed water flow several times at a pressure of 4 MPa from the upper layer side and 3 MPa from the lower layer side to promote the single fiberization of the fibers that constitute the fiber bundle.
[0268] Next, the fiber sheet is impregnated with an impregnation solution containing 9.0% (in terms of mass %) of an average primary particle size of 0.3 μm, a polyether-based aqueous PU dispersion "AE-12" (manufactured by Nikka Chemical Co., Ltd.) (solid content concentration: 35 mass %), 3.0% by weight of anhydrous sodium sulfate as an impregnation aid in the impregnation solution (in terms of mass %), and PVA resin particles "NL-05" (manufactured by Mitsubishi Chemical Corporation) with an average particle size of 3 μm. Then, the fiber sheet is wet-heat coagulated at 100°C for 5 minutes and dried with hot air at 130°C to 150°C for 2 to 6 minutes using a pin tenter dryer.
[0269] Then, the sheet was immersed in hot water heated to 95°C to extract and remove the impregnated anhydrous sodium sulfate and PVA resin particles, thereby obtaining a sheet filled with a water-dispersible PU resin, wherein the ratio of the water-dispersible PU resin to the total fiber mass of the sheet was 30% by mass.
[0270] Thereafter, the sheet was cut in half perpendicularly to the thickness direction using a half-cutting machine with a circular manual cutter, and the surface not cut in half was subjected to a napping treatment using #400 sandpaper, and then dyed with a blue disperse dye ("BlueFBL" manufactured by Sumitomo Chemical Co., Ltd.) having a dye concentration of 5.0% owf at 130° C. for 15 minutes using a jet dyeing machine, and then reduced and cleaned. Thereafter, it was dried at 100° C. for 5 minutes using a pin tenter dryer to obtain a single-layer artificial leather.
[0271] [Example 2]
[0272] Artificial leather was obtained in the same manner as in Example 1 except that the turbulence in the water flow dispersion treatment was changed to 13%.
[0273] [Example 3]
[0274] Artificial leather was obtained in the same manner as in Example 1 except that the turbulence in the water flow dispersion treatment was changed to 11%.
[0275] [Example 4]
[0276] Artificial leather was obtained in the same manner as in Example 1 except that the turbulence in the water flow dispersion treatment was changed to 7%.
[0277] [Example 5]
[0278] Artificial leather was obtained in the same manner as in Example 1 except that the pressure on the upper layer side of the high-speed water flow was changed to 5.5 MPa.
[0279] [Example 6]
[0280] Artificial leather was obtained in the same manner as in Example 1 except that the pressure on the upper layer side of the high-speed water flow was changed to 12.0 MPa.
[0281] [Example 7]
[0282] Artificial leather was obtained in the same manner as in Example 1 except that the nozzle hole diameter in the water jet dispersion treatment was changed to 0.15 mm.
[0283] [Example 8]
[0284] Artificial leather was obtained in the same manner as in Example 1 except that the nozzle hole diameter in the water jet dispersion treatment was changed to 0.22 mm.
[0285] [Example 9]
[0286] Artificial leather was obtained in the same manner as in Example 1 except that the nozzle hole interval in the water jet dispersion treatment was changed to 0.50 mm.
[0287] [Example 10]
[0288] Artificial leather was obtained in the same manner as in Example 1 except that the nozzle hole interval in the water flow dispersion treatment was changed to 0.50 mm and the nozzle hole row was changed to one row.
[0289] [Example 11]
[0290] Artificial leather was obtained in the same manner as in Example 1 except that the nozzle hole interval in the water flow dispersion treatment was changed to 0.90 mm and the nozzle hole row was changed to one row.
[0291] [Example 12]
[0292] Artificial leather was obtained in the same manner as in Example 1 except that the average particle size of the PVA resin fine particles was changed to 1.5 μm.
[0293] [Example 13]
[0294] Artificial leather was obtained in the same manner as in Example 1 except that the average particle size of the PVA resin fine particles was changed to 7.0 μm.
[0295] [Example 14]
[0296] Artificial leather was obtained in the same manner as in Example 1 except that the ratio of the PU resin to the fiber sheet was 24% by mass.
[0297] [Example 15]
[0298] Artificial leather was obtained in the same manner as in Example 1 except that the ratio of the PU resin to the fiber sheet was 43% by mass.
[0299] [Comparative Example 1]
[0300] Artificial leather was obtained in the same manner as in Example 1 except that the water jet dispersion treatment was not performed.
[0301] [Comparative Example 2]
[0302] Artificial leather was obtained in the same manner as in Example 1 except that PVA resin fine particles were not added to the PU resin impregnation solution.
[0303] [Comparative Example 3]
[0304] Artificial leather was obtained in the same manner as in Example 1 except that the average particle size of the PVA resin fine particles was changed to 0.5 μm.
[0305] [Comparative Example 4]
[0306] Artificial leather was obtained in the same manner as in Example 1 except that the average particle size of the PVA resin fine particles was changed to 11 μm.
[0307] [Comparative Example 5]
[0308] Artificial leather was obtained in the same manner as in Example 1 except that the ratio of the PU resin to the fiber sheet was 14% by mass.
[0309] [Comparative Example 6]
[0310] Artificial leather was obtained in the same manner as in Example 1 except that the ratio of the PU resin to the fiber sheet was 53% by mass.
[0311] The results of Examples 1 to 15 and Comparative Examples 1 to 6 are shown in Table 1 below.
[0312] [Table 1]
[0313]
[0314] It can be seen from these results that in each embodiment, by making the k-neighbor distance ratio value (k=9, radius r=20μm) between the single fiber cross sections constituting the fiber layer (A) greater than 10% and less than 80%, and the cross-sectional PU resin area ratio in the thickness direction cross section greater than 10% and less than 30%, and the standard deviation of the cross-sectional PU resin area ratio is less than 25%, the PU resin and the single fiber are distributed in a specific structure, thereby obtaining artificial leather that takes into account texture (softness and hardness value), density and moistness.
[0315] Industrial Applicability
[0316] The artificial leather of the present invention has excellent texture (hardness value), dense feeling and moist feeling, and therefore can be suitably used for surface materials or interior materials of sheets for interior decoration, automobiles, airplanes, trains, etc., clothing products, etc. Specifically, the artificial leather of the present invention can be suitably used as surface materials for furniture, chairs, wall materials, seats, ceilings, interiors, etc. in the compartments of automobiles, trains, airplanes, etc.; interior materials with very beautiful appearance, uppers of shirts, coats, casual shoes, sports shoes, men's shoes, women's shoes, etc., laces, etc., bags, belts, wallets, etc., clothing materials used as parts thereof, wiping cloths, polishing cloths, CD curtains, etc., industrial materials.
[0317] Description of Reference Numerals
[0318] 1 Fiber sheet
[0319] 11 loose cloth (optional)
[0320] 12 Fiber layer (A)
[0321] 13 Fiber layer (B)
[0322] A The cross section of the fiber when the cross section is elliptical
[0323] a The longest diameter of section A
[0324] b A straight line passing through the midpoint p of the longest diameter a and perpendicular to the longest diameter a
[0325] c The distance between the outer circumferences on line b
[0326] p midpoint of the longest diameter a
[0327] MD Machine Direction
[0328] CD width (horizontal) direction
[0329] t Thickness of artificial leather
Claims
1. An artificial leather, characterized in that: The present invention relates to an artificial leather comprising a fiber sheet and a polyurethane resin, wherein the fiber sheet comprises at least a fiber layer (A), wherein the fiber layer (A) constitutes a first outer surface of the artificial leather, and The ratio of k-neighbor distances between the cross sections of single fibers constituting the fiber layer (A) in the cross section in the thickness direction of the artificial leather is 10% or more and 80% or less, wherein k=9 and radius r=20 μm; and The cross-sectional polyurethane resin area ratio in the cross section in the thickness direction of the fiber layer (A) is 10% or more and 30% or less, and The standard deviation of the cross-sectional polyurethane resin area ratio in the cross section in the thickness direction of the fiber layer (A) is 25% or less, The polyurethane resin is a water-dispersible polyurethane resin.
2. The artificial leather according to claim 1, wherein The k nearest neighbor distance ratio value is greater than or equal to 30% and less than or equal to 60%.
3. The artificial leather according to claim 1, wherein The cross-sectional polyurethane resin area ratio of the fiber layer (A) in the cross section in the thickness direction is 15% to 26%.
4. The artificial leather according to claim 1, wherein The standard deviation of the cross-sectional polyurethane resin area ratio in the cross section in the thickness direction of the fiber layer (A) is 20% or less.
5. The artificial leather according to claim 1, wherein In the three-dimensional image of the fiber layer (A) based on X-ray CT, the diameter of the largest sphere entering the space obtained by removing the fibers constituting the fiber layer (A) and the polyurethane resin, that is, the average value of the spatial dimension in the thickness direction of the fiber layer (A), that is, the average spatial dimension is greater than 5 μm and less than 35 μm.
6. The artificial leather according to claim 5, wherein The average space size is 5 μm or more and 25 μm or less.
7. The artificial leather according to any one of claims 1 to 6, wherein The fiber sheet has a two-layer or more structure consisting of a fiber layer (A) constituting the first outer surface and a loose scrim and / or a fiber layer (B) in contact with the fiber layer (A).
8. The artificial leather according to any one of claims 1 to 6, wherein The fiber sheet has a three-layer structure, and the loose cloth is the middle layer.
9. The artificial leather according to any one of claims 1 to 6, wherein The average diameter of single fibers constituting the fiber layer (A) is 1.0 μm or more and 8.0 μm or less.
10. The artificial leather according to any one of claims 1 to 6, wherein The adhesion rate of the polyurethane resin to the fiber sheet is 15 mass % or more and 50 mass % or less.
11. The artificial leather according to claim 10, wherein The adhesion rate of the polyurethane resin to the fiber sheet is 22 mass % or more and 45 mass % or less.
12. The artificial leather according to any one of claims 1 to 6, which has a softness and hardness value of 28 cm or less.
13. The artificial leather according to any one of claims 1 to 6, wherein The fiber sheet is composed of polyester fibers.
14. The artificial leather according to any one of claims 1 to 6, which has a density level of 4.0 or higher.
15. A method for producing the artificial leather according to any one of claims 1 to 14, comprising the following steps: A process of forming a fiber web with sea-island staple fibers, then subjecting the fiber web to a needle punching treatment, and subjecting the fiber sheet thus obtained to a sea-removing treatment to obtain a fiber sheet in which single fibers of the island component are exposed; The step of subjecting the obtained fiber sheet to water flow dispersion treatment to obtain a fiber sheet in which single fibers are dispersed; A step of impregnating the obtained fiber sheet in which single fibers are dispersed with an aqueous polyurethane resin dispersion containing hot water-soluble resin microparticles having an average particle size of 1 μm to 8 μm so that the adhesion rate of the polyurethane resin to 100% by mass of the fiber sheet becomes 15% to 50% by mass, and then heating the polyurethane resin to adhere the polyurethane resin to obtain a sheet-like object filled with the polyurethane resin; and A step of removing the hot water-soluble resin fine particles from the obtained sheet-like product using hot water.
16. The manufacturing method according to claim 15, wherein: The hot water-soluble resin particles are polyvinyl alcohol resin.
17. The manufacturing method according to claim 15 or 16, wherein: The water flow dispersion treatment is performed using a plurality of nozzles having a nozzle hole interval of 1.0 mm or less and a nozzle hole diameter of 0.05 mm or more and 0.30 mm or less.
18. The manufacturing method according to claim 17, wherein: The water flow dispersion treatment is performed using a plurality of nozzles having nozzle hole intervals of 0.60 mm or less.
19. The manufacturing method according to claim 17, wherein: The water flow dispersion treatment is performed using a plurality of nozzles having a nozzle hole diameter of 0.08 mm or more and 0.22 mm or less.
20. The manufacturing method according to claim 15 or 16, wherein: The spraying is performed under the condition that the water pressure of the water flow dispersion treatment is 1.0 to 10.0 MPa.
21. The manufacturing method according to claim 15 or 16, wherein: The water flow dispersion treatment is performed using a plurality of nozzles that eject water flows with a turbulent flow of 10% or more.
22. The manufacturing method according to claim 21, wherein: The water flow dispersion treatment is performed using a plurality of nozzles that eject water flows having a turbulent flow of 12% or more.
23. The manufacturing method according to claim 15 or 16, wherein: The solid content concentration of the aqueous polyurethane resin dispersion is 10% by weight or more and 35% by weight or less.
24. The manufacturing method according to claim 15 or 16, wherein: The content of the hot water-soluble resin fine particles in the water-dispersible polyurethane resin dispersion is 1% by weight or more and 20% by weight or less.
25. The manufacturing method according to claim 15 or 16, wherein: The hot water-soluble resin fine particles have an average particle size of 2 μm or more and 4 μm or less.
Citation Information
Patent Citations
Production of fine polyvinyl alcohol particle
JP1995082384A
Method for producing sheet-shaped material
JP2014025165A
Sheet-shaped material and method for manufacturing the same
JP2015161040A
Substrate for artificial leather
JP2017008478A
Sheet-like material and method for producing same
WO2015129602A1